Composite positive electrode active material, positive electrode and lithium battery each containing the same, and method for producing the same

By covering metal oxides with different crystal structures on the lithium nickel transition metal oxides to form a composite positive electrode active material, the side reaction and thermal stability problems in nickel batteries are solved, and the cycle characteristics and life of the lithium battery are improved.

CN111009640BActive Publication Date: 2024-12-20SAMSUNG ELECTRONICS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201910864597.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-10-04
Filing Date
2019-09-12
Publication Date
2024-12-20
Estimated Expiration
2039-12-25

AI Technical Summary

Technical Problem

Nickel-based positive electrode active material has deteriorated battery performance due to poor side reactions and thermal stability in lithium batteries. A method is needed to suppress side reactions to improve the life and thermal stability of lithium batteries.

Method used

Using a composite positive electrode active material, the material is made of lithium nickel transition metal oxide as the core, and the outer layer is coated with the first and second metal oxides with different crystal structures, and a multi-layer or single-layer shell structure is formed by heat treatment to suppress nickel. Ion leakage and side reactions.

Benefits of technology

It effectively suppresses nickel ion leakage and side reactions, improves the circulation characteristics and thermal stability of lithium batteries, extends the service life of the battery, and maintains high capacity characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111009640B_ABST
    Figure CN111009640B_ABST
Patent Text Reader

Abstract

A composite positive electrode active material, a positive electrode and a lithium battery each containing the same, and a method for manufacturing the same. The composite positive electrode active material comprises: a core comprising a plurality of primary particles and a shell disposed on the core, wherein the primary particles of the plurality of primary particles comprise lithium nickel transition metal oxide, the shell comprises a first component and a second component, wherein the first component contains a first metal and the second component contains a second metal, wherein the first metal comprises a metal of Groups 2, 4, 5, and 7 to 15, the second metal comprises a metal of Group 3, and the first component comprises a first phase and the second component comprises a second phase distinguishable from the first phase.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2018-0118138 filed in the Korean Intellectual Property Office on October 4, 2018, and all rights arising therefrom, the contents of which are incorporated herein in their entirety by reference. Technical Field

[0003] The present disclosure relates to a composite cathode active material, a cathode and a lithium battery each including the same, and a method for preparing the composite cathode active material. Background Art

[0004] For miniaturization and high performance of various devices, it is important that lithium batteries have high energy density in addition to reduced size and weight. That is, high-capacity lithium batteries are desirable.

[0005] High capacity positive electrode active materials can be used to provide lithium batteries with high capacity.

[0006] A nickel-based positive active material may have poor lifespan characteristics and poor thermal stability due to a high amount of residual lithium on its surface and a side reaction caused by cation mixing.

[0007] Therefore, there is a need for a method that can prevent degradation of battery performance even when a nickel-based positive electrode active material is used. Summary of the invention

[0008] Provided is a composite cathode active material capable of preventing degradation of battery performance due to suppression of a side reaction of the composite cathode active material.

[0009] A positive electrode including the composite positive electrode active material is provided.

[0010] A lithium battery including the positive electrode is provided.

[0011] A method for preparing the composite positive electrode active material is provided.

[0012] Additional aspects will be set forth in part in the description which follows and, in part, will be apparent from the description, or may be learned by practice of the presented embodiments.

[0013] According to aspects of an embodiment, a composite positive electrode active material includes:

[0014] a core comprising a plurality of primary particles; and

[0015] a shell disposed on the core,

[0016] in

[0017] The primary particles of the plurality of primary particles include lithium nickel transition metal oxide, and

[0018] The shell includes a first component and a second component, wherein the first component contains a first metal and the second component contains a second metal,

[0019] in

[0020] The first metal includes at least one metal other than nickel belonging to any one of Groups 2, 4, 5, and 7 to 15 of the Periodic Table of Elements,

[0021] The second metal comprises a metal of Group 3 of the Periodic Table of Elements, and

[0022] The first component includes a first phase and the second component includes a second phase distinguishable from the first phase.

[0023] According to an aspect of an embodiment, a positive electrode includes the composite positive electrode active material.

[0024] According to an aspect of an embodiment, a lithium battery includes the positive electrode.

[0025] According to aspects of an embodiment, a method for preparing a composite positive active material includes:

[0026] Providing lithium nickel transition metal oxides;

[0027] contacting a first metal precursor, a second metal precursor, and the lithium nickel transition metal oxide to prepare a mixture;

[0028] drying the mixture; and

[0029] The dried mixture is heat-treated at a temperature of 400° C. to 1000° C. under an oxidative atmosphere to produce the composite positive active material. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] These and / or other aspects will become apparent and more readily appreciated from the following description of the embodiments considered in conjunction with the accompanying drawings, in which:

[0031] Figure 1A A schematic diagram showing a partial view of an embodiment illustrating the internal structure of a composite positive electrode active material;

[0032] Figure 1B A schematic cross-sectional view showing an embodiment of a composite positive electrode active material;

[0033] Figure 2A is a graph of intensity (arbitrary unit (au)) versus diffraction angle (degrees, 2θ) and shows the results of X-ray diffraction ("XRD") analysis of the composite positive active materials of Examples 1 and 2 and Comparative Examples 3 and 4;

[0034] Figure 2B show Figure 2A an enlarged view of a portion of;

[0035] Figures 3A-3E Scanning electron microscope ("SEM") images showing the surfaces of the composite positive active materials of Comparative Examples 1, 3 and 4 and Examples 1 and 2;

[0036] Figures 4A-4C A high angle annular dark field ("HAADF") scanning transmission electron microscope ("STEM") image and an energy dispersive X-ray spectroscopy ("EDS") image showing a cross section of the composite cathode active material of Example 1; and

[0037] Figure 5 A schematic diagram showing an embodiment of a lithium battery. DETAILED DESCRIPTION

[0038] Embodiments will now be described in detail, examples of which are shown in the accompanying drawings, wherein the same reference numerals represent the same elements throughout. In this regard, the present embodiment may have different forms and should not be construed as being limited to the description set forth herein. Therefore, the embodiments are described below only by reference to the accompanying drawings to illustrate aspects. As used herein, the term "and / or" includes any and all combinations of one or more of the relevant listed items. Expressions such as "at least one (individual) of..." modify the entire list of elements when before or after a list of elements, rather than modifying the individual elements of the list.

[0039] The disclosed embodiments may have a variety of variations. Therefore, examples are shown in the drawings and will be described in detail. However, it will be understood that this is not intended to limit the disclosure to any specific embodiment, but is intended to cover all conversions, equivalents or substitutes falling within the scope of the present disclosure.

[0040] The terms used herein are only for describing specific examples and are not intended to be limiting. The singular forms "a, an" and "the" include plural indicators unless the context clearly specifies otherwise. Hereinafter, it will be understood that the terms used herein such as "include", "have" and "comprise" are intended to indicate the presence of features, quantities, steps, actions, components, parts or combinations thereof disclosed in the specification, without excluding the possibility that one or more other features, quantities, steps, actions, components, parts or combinations thereof may be present or may be added. The expression " / " may be interpreted as "and" or "or" depending on the context.

[0041] In the drawings, the thickness may be enlarged or reduced to clearly represent the layers and regions. Throughout the specification, the same elements are represented by the same reference numerals. It will be understood that when a layer, film, region or panel is referred to as being "formed on" another layer, film, region or panel, it may be formed directly or indirectly on the other layer, film, region or panel. Throughout the specification, the first, second, etc. terms may be used to describe a variety of components (assemblies), but the components (assemblies) should not be limited by these terms. These terms are only used to distinguish one component from another.

[0042] As used herein, "about" includes the stated value and means within an acceptable range of deviation for a particular value as determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" can mean within one or more standard deviations of the stated value, or within ±30%, 20%, 10%, or 5%.

[0043] Unless otherwise defined, all terms (including technical and scientific terms) used in this article have the same meaning as commonly understood by ordinary technicians in the field to which the present disclosure belongs. It will be further understood that terms, such as those defined in commonly used dictionaries, should be interpreted as their meanings consistent with their meanings in the context of the present disclosure and the relevant art, and will not be interpreted in an idealized or excessive formal sense unless clearly defined in this article.

[0044] Exemplary embodiments are described herein with reference to schematically illustrated cross-sectional views as idealized embodiments. As such, deviations from the illustrated shapes as a result of, for example, manufacturing techniques and / or tolerances are to be expected. Therefore, the embodiments described herein should not be construed as being limited to the specific shapes of the regions as illustrated herein, but rather include deviations in shape resulting from, for example, manufacturing. For example, a region illustrated or described as flat may typically have rough and / or nonlinear features. Moreover, illustrated sharp corners may be rounded. Therefore, the regions illustrated in the figures are schematic in nature and their shapes are not intended to illustrate the precise shape of the regions and are not intended to limit the scope of the claims.

[0045] The C rate is a measure of the rate at which a battery is discharged relative to its maximum capacity. A 1.0 C rate is the discharge current that discharges the entire battery in 1 hour, e.g., for a battery with a discharge capacity of 1.6 amp-hours, a 1.0 C rate is a discharge current of 1.6 amps. For example, for this battery, a 5.0 C rate is 8.0 amps. For example, for this battery, a 0.5 C rate is 0.8 amps.

[0046] Hereinafter, a composite cathode active material, a cathode including the composite cathode active material, a lithium battery including the composite cathode active material, and a method of preparing the composite cathode active material will be described in detail.

[0047] The composite positive active material according to the embodiment includes: a core including a plurality of primary particles; and a shell disposed on the core, wherein the primary particles of the plurality of primary particles include lithium nickel transition metal oxide, and the shell includes a first component containing a first metal and a second component containing a second metal, and the first metal includes at least one metal other than nickel belonging to Group 2, Group 4, Group 5, or any one of Groups 7 to 15 of the periodic table, and the second metal includes a metal of Group 3 of the periodic table, and the first component includes a first phase and the second component includes a second phase that can be distinguished from the first phase. For example, the first metal includes at least one metal other than nickel belonging to Group 2, Group 4, Group 5, and any one of Groups 7 to 15 of the periodic table.

[0048] Reference Figure 1A , the composite positive active material 300 includes: a core 100 including a plurality of primary particles 10 and a shell 200 located on the core 100. The core 100 is a secondary particle containing the primary particles 10. The primary particles 10 may be, for example, microcrystals having the same crystal structure. The primary particles 10 include lithium nickel transition metal oxide, and the shell 200 may include a first component including a first metal and a second component including a second metal. The first metal may include at least one metal belonging to any one of Group 2, Group 4, Group 5, or Group 7 to Group 15 of the periodic table other than nickel, and the second metal may include a metal of Group 3 of the periodic table. The first component may include a first phase and the second component includes a second phase that can be distinguished from the first phase. The lithium nickel transition metal oxide may have a layered crystal structure.

[0049] Hereinafter, the embodiments will be further disclosed, and the theoretical basis supporting the composite positive electrode active material according to the embodiments provides excellent effects. However, this description is provided only to help the understanding of the present disclosure, and in view of any aspect, the scope of the present disclosure should not be limited.

[0050] The shell 200 including the first component containing the first metal is disposed on the core 100 of the composite positive electrode active material 300, for example, to suppress the leakage (leakage) of nickel ions from the core 100 into the electrolyte solution. Due to the heat treatment included in the process of manufacturing the shell including the first component, the suppression of leakage of nickel ions from the core 100 to the electrolyte solution, such as dilution or elution, can be reduced. Since the second component containing the second metal is additionally included, for example, the leakage of nickel ions from the core 100 into the electrolyte solution can be effectively suppressed. When the shell 200 including the first component and the second component is formed, the precursor of the first component and the precursor of the second component can be combined with the lithium compound (for example, Li 2 CO 3 or LiOH) to reduce the amount of lithium compounds remaining on the surface of the composite positive active material 300. Therefore, and although not wishing to be bound by theory, it is understood that the side reactions occurring between the composite positive active material 300 and the electrolyte solution and the gas generation are effectively suppressed. The first component may include a first phase and the second component includes a second phase that can be distinguished from the first phase. In an embodiment, the first phase is different from the second phase in terms of crystal structure. Since the second component includes a second phase that can be distinguished from the first phase and has improved structure and thermal stability, the side reactions between the composite positive active material 300 and the electrolyte solution are suppressed, resulting in stabilization of the surface of the composite positive active material 300. The second phase included in the second component may have improved ionic conductivity and electronic conductivity. Therefore, the interface resistance between the composite positive active material and the electrolyte solution is reduced. Therefore, although the shell 200 includes the second component, the internal resistance of the lithium battery including the composite positive active material 300 can be maintained or reduced. As a result, the cycle characteristics and thermal stability of the lithium battery including the composite positive active material 300 are improved.

[0051] In the composite positive active material 300, the amount of nickel included in the lithium nickel transition metal oxide may be about 70 mol% or more, about 71 mol% or more, about 75 mol% or more, about 80 mol% or more, about 85 mol% or more, about 90 mol% or more, about 93 mol% or more, about 95 mol% or more, or about 97 mol% or more, based on the total moles of nickel and transition metals in the lithium nickel transition metal oxide. In the composite positive active material 300, the amount of nickel in the lithium nickel transition metal oxide may be about 99.9 mol% or less, 99 mol% or less, or 98 mol% or less, for example, about 70 mol% to about 99 mol%, or about 75 mol% to about 95 mol%, based on the total moles of nickel and transition metals in the lithium nickel transition metal oxide. Since the amount of nickel in the lithium nickel transition metal oxide is about 70 mol% or more, a high capacity can be provided. Therefore, a lithium battery with a high capacity can be provided.

[0052] The first component may have, for example, a phase having a layered crystal structure, a phase having a spinel crystal structure, or a combination thereof. The first component may have, for example, a layered crystal structure, and may belong to the space group R-3m. The first component may have, for example, a spinel crystal structure, and may belong to the space group Fd-3m. Since the first component has such a phase, the cycle characteristics and thermal stability of the lithium battery are further improved.

[0053] The second component may have, for example, a phase having a fluorite (fluorspar) crystal structure. The second component may have, for example, a fluorite crystal structure belonging to the Fm-3m space group. Since the second component has such a phase, the cycle characteristics and thermal stability of the lithium battery are further improved.

[0054] The shell may have, for example, a multilayer structure including a first layer including the first component and a second layer including the second component, a single layer structure including the first component and the second component, or a combination thereof.

[0055] When the shell has a multilayer structure, a first layer including the first component may be provided on the core of the secondary particle and the primary particle constituting the core, and a second layer including the second component is provided on the first layer. Since the composite positive electrode active material has a shell having a multilayer structure, the cycle characteristics and thermal stability of a lithium battery including such a composite positive electrode active material are improved.

[0056] In an embodiment, the first layer is provided on the primary particles constituting the core, and the concentration of the first metal contained in the first layer is greater than the concentration of the first metal contained in the primary particles. Figure 4C, the first layer is located on the primary particles constituting the core, and the concentration of Co contained in the first layer is greater than the concentration of Co contained in the primary particles. Figure 4B and 4C The greater the concentration, the brighter the color. For example, the concentration per unit area of ​​the first metal contained in the first layer is greater than the concentration per unit area of ​​the first metal contained in the primary particles.

[0057] In the composite positive electrode active material, for example, the thicknesses of the first layer and the second layer included in the shell having a multilayer structure are the same or different from each other. For example, when the second layer is thicker than the first layer, the leakage of metal ions and the side reaction between the composite positive electrode active material and the electrolyte solution are more effectively suppressed. For example, when the second layer is thinner than the first layer, the increase in the resistance of the composite positive electrode active material caused by the second layer is minimized, and the side reaction between the composite positive electrode active material and the electrolyte solution is suppressed. Therefore, despite the addition of the second layer, the cycle characteristics of the lithium battery including the composite positive electrode active material are improved.

[0058] The thickness of the first layer is, for example, 50 nanometers (nm) or less, 40nm or less, 30nm or less, 20nm or less, 10nm or less, or 5nm or less. The thickness of the first layer is, for example, in the range of about 1nm to about 50nm, about 1nm to about 40nm, about 1nm to about 30nm, about 1nm to about 20nm, about 1nm to about 10nm, or about 1nm to about 5nm. Since the thickness of the first layer is within these ranges, the cycle characteristics and thermal stability of the lithium battery can be further improved. In an embodiment, when the thickness of the second layer is the same as or less than the thickness of the first layer, the thickness of the second layer is, for example, 50 nanometers (nm) or less, 40nm or less, 30nm or less, 20nm or less, 10nm or less, or 5nm or less, and the thickness of the second layer is, for example, in the range of about 1nm to about 50nm, about 1nm to about 40nm, about 1nm to about 30nm, about 1nm to about 20nm, about 1nm to about 10nm, or about 1nm to about 5nm. In an embodiment, when the thickness of the second layer is greater than the thickness of the first layer, the thickness of the second layer may be, for example, 500 nm or less, 400 nm or less, 300 nm or less, 200 nm or less, 100 nm or less, or 50 nm or less. In an embodiment, the thickness of the second layer may be, for example, in the range of about 10 nm to about 500 nm, about 10 nm to about 400 nm, about 10 nm to about 300 nm, about 10 nm to about 200 nm, about 10 nm to about 100 nm, or about 10 nm to about 50 nm. Since the thickness of the second layer is within these ranges, the cycle characteristics and thermal stability of the lithium battery can be further improved.

[0059] In an embodiment, the shell may have a monolayer (e.g., single layer) structure. Since the shell has a monolayer structure, the third layer including both the first component and the second component may be provided on the core as a secondary particle and the primary particles constituting the core. Since the composite positive active material has a shell having a monolayer structure, the cycle characteristics and thermal stability of a lithium battery including such a composite positive active material are improved.

[0060] The thickness of the shell including the first layer and the second layer or the third layer in the composite positive active material may be, for example, 550nm or less, 450nm or less, 350nm or less, 250nm or less, 150nm or less, or 50nm or less. The thickness of the shell may be, for example, in the range of about 1nm to about 550nm, about 1nm to about 450nm, about 1nm to about 350nm, about 1nm to about 250nm, about 10nm to about 150nm, or about 10nm to about 50nm. Since the thickness of the shell is within these ranges, the cycle characteristics and thermal stability of the lithium battery can be further improved.

[0061] In the composite positive electrode active material, the shell completely or partially covers the surface of the core. In an embodiment, the shell covers 10% or more, 20% or more, 30% or more, 40% or more, or 50% or more of the core. In an embodiment, the shell covers 99.9% or less, 99% or less, 95% or less, 90% or less of the core. The shell located on the core may be discontinuous, i.e., island-shaped, or may be continuous. Reference Figures 4A to 4C The shell is, for example, disposed on at least two primary particles exposed on the surface of the core. In an embodiment, the shell covers the entirety of the core.

[0062] In an embodiment, the first component included in the shell may be provided on a primary particle constituting the core and / or a secondary particle corresponding to the core.

[0063] In an embodiment, the first metal contained in the first component may be Co, Mg, Zr, Al, Mn, Si, Pd, Ti, Sn, Ir, Pt, Ru, Ca, Ba, V, Nb, Fe, Cu, Ag, Zn, B, Ga, Ge, Sb, Bi, or a combination thereof. Since the first component includes the first metal, the cycle characteristics and thermal stability of the lithium battery including the composite positive active material are improved. Since the first layer includes, for example, Co that provides a discharge capacity, the capacity of the composite positive active material is prevented from decreasing. When the first layer includes, for example, Mg, the structural stability of the composite positive active material is improved, and thus the life characteristics of the lithium battery including the composite positive active material can be improved. As used herein, "metal", such as a first metal or a second metal includes metalloids such as Si and B.

[0064] The first component of the composite positive active material may be, for example, a component including the first metal and oxygen, or a component including lithium, the first metal and oxygen. The first component may include, for example, about 0 mol to about 3.3 mol of lithium (based on 1 mol of the first component), about 0.7 mol to about 3.3 mol of the first metal (based on 1 mol of the first component), and about 1.7 mol to about 4.3 mol of oxygen (based on 1 mol of the first component). The first component may include, for example, about 0 mol to about 3.2 mol of lithium (based on 1 mol of the first component), about 0.8 mol to about 3.2 mol of the first metal (based on 1 mol of the first component), and about 1.8 mol to about 4.2 mol of oxygen (based on 1 mol of the first component). The first component may include, for example, about 0 mol to about 3.1 mol of lithium (based on 1 mol of the first component), about 0.9 mol to about 3.1 mol of the first metal (based on 1 mol of the first component), and about 1.9 mol to about 4.1 mol of oxygen (based on 1 mol of the first component). Since the first component has these composition ratios, the cycle characteristics and thermal stability of the lithium battery including the composite positive active material are improved.

[0065] The first component has a composition represented by, for example, the following Formula 1:

[0066] Formula 1

[0067] Li a M1 b O c

[0068] Wherein, in Formula 1, M1 is Co, Mg, Zr, Al, Mn, Si, Pd, Ti, Sn, Ir, Pt, Ru, Ca, Ba, V, Nb, Fe, Cu, Ag, Zn, B, Ga, Ge, Sb, Bi, or a combination thereof, and satisfies the conditions of 0≤a≤3.1, 0.9≤b≤3.1, and 1.9≤c≤4.1.

[0069] The first component may include, for example, Co 3 O 4 、MgO、Li x CoO 2 (0 <x≤1.5)、Li 2 ZrO 3 、ZrO 2 、Al 2 O 3 , Li 2 MnO 3 、LiMn 2 O 4 、LiAlO 2 、TiO 2 , Li 2 TiO3 , Li 2 SnO 3 、SnO、SnO 2 、BaTiO 3 、V 2 O 5 , Nb 2 O 5 , ZnO, B 2 O 3 , Ga 2 O 3 , or a combination thereof.

[0070] In the composite positive electrode active material, the amount of the first metal or the first component included in the first layer or the third layer may be, for example, 10 parts by weight or less, 5 parts by weight or less, 4 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, or 1 part by weight or less, based on 100 parts by weight of the lithium nickel transition metal oxide. The amount of the first metal or the first component included in the first layer or the third layer may be, for example, about 0.01 parts by weight to about 10 parts by weight, about 0.05 parts by weight to about 5 parts by weight, about 0.1 parts by weight to about 4 parts by weight, about 0.1 parts by weight to about 3 parts by weight, about 0.1 parts by weight to about 2 parts by weight, or about 0.1 parts by weight to about 1 part by weight, based on 100 parts by weight of the lithium nickel transition metal oxide. Since the first layer or the third layer has such a range of the first component or the first metal, the cycle characteristics and thermal stability of the lithium battery including the composite positive electrode active material are improved.

[0071] The second component in the composite positive active material may be, for example, a component including the second metal and oxygen. The second component may include, for example, about 0.7 mol to about 1.3 mol of the second metal (based on 1 mol of the second component) and about 1.7 mol to about 2.3 mol of oxygen (based on 1 mol of the second component). The second component may include, for example, about 0.8 mol to about 1.2 mol of the second metal (based on 1 mol of the second component) and about 1.8 mol to about 2.2 mol of oxygen (based on 1 mol of the second component). The second component may include, for example, about 0.9 mol to about 1.1 mol of the second metal (based on 1 mol of the second component) and about 1.9 mol to about 2.1 mol of oxygen (based on 1 mol of the second component). Since the second component has these composition ratios, the cycle characteristics and thermal stability of the lithium battery including the composite positive active material are improved.

[0072] The second component has a composition represented by, for example, the following Formula 2:

[0073] Formula 2

[0074] M2b O c

[0075] Wherein, in Formula 2, M2 is Ce, La, Sc, Y, Nd, Sm, Er, or a combination thereof, and satisfies the conditions of 0.9≤b≤1.1 and 1.9≤c≤2.1.

[0076] The second component may include, for example, CeO 2 、Ce 2 O 3 、Ce 3 O 4 ,La 2 O 3 Sc 2 O 3 , Y 2 O 3 、Nd 2 O 3 、Sm 2 O 3 , Er 2 O 3 , or a combination thereof.

[0077] In the composite positive electrode active material, the amount of the second metal or the second component included in the second layer or the third layer may be, for example, 10 parts by weight or less, 5 parts by weight or less, 4 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, or 1.5 parts by weight or less, based on 100 parts by weight of the lithium nickel transition metal oxide. The amount of the second metal or the second component included in the second layer or the third layer may be, for example, independently, about 0.01 parts by weight to about 10 parts by weight, about 0.05 parts by weight to about 5 parts by weight, about 0.1 parts by weight to about 4 parts by weight, about 0.1 parts by weight to about 3 parts by weight, about 0.1 parts by weight to about 2 parts by weight, or about 0.1 parts by weight to about 1.5 parts by weight, based on 100 parts by weight of the lithium nickel transition metal oxide. Since the second layer or the third layer has such a range of the second component or the second metal, the cycle characteristics and thermal stability of the lithium battery including the composite positive electrode active material are improved.

[0078] In an embodiment, the second component may be disposed on primary particles constituting the core and / or secondary particles corresponding to the core. For example, the second component may be disposed on the first layer, the core, or a combination thereof.

[0079] Reference Figure 1A and 1BIn the composite positive active material 300, the core 100 includes a grain boundary 20 located between the primary particles 10 and adjacent to the primary particles 10, wherein the grain boundary 20 includes a third component containing a third metal. Since the grain boundary 20 adjacent to the primary particles 10 between the primary particles 10 constituting the core 100 of the composite positive active material 300 includes the third component, lithium ions are smoothly conducted in the core 100, for example, with reduced concentration polarization, and nickel ions can be suppressed from leaking or eluting from the primary particles 10 in the core 100 to the electrolyte solution that can penetrate into the core 100. In addition, the side reaction between the electrolyte solution and the primary particles 10 in the core 100 is suppressed. Therefore, the cycle characteristics of the lithium battery including the composite positive active material 300 are improved. In addition, the amount of lithium remaining on the surface of the primary particles 10 located in the core 100 is reduced, and thus the degradation of the composite positive active material 300 is suppressed and less gas is generated, resulting in an increase in the thermal stability of the lithium battery. Although not wishing to be bound by theory, it is understood that the third component between the primary particles 10 and adjacent to the grain boundaries 20 of the primary particles 10 prevents surface damage of the primary particles 10 that occurs during the washing process of the composite positive electrode active material 300 and prevents reduction in the life characteristics of the lithium battery. The third component between the primary particles 10 and adjacent to the grain boundaries 20 of the primary particles 10 buffers the volume change of the primary particles 10 during the charge and discharge cycle, resulting in suppression of cracks between the primary particles 10, and even after long-term charge and discharge, suppresses the reduction in the mechanical strength of the composite positive electrode active material 300, and prevents the degradation of the lithium battery. In addition, since the third component in the lithium nickel transition metal oxide included in the primary particles 10 includes the third metal, the crystal structure of the lithium nickel transition metal oxide is stabilized, and thus the cycle characteristics of the lithium battery including the composite positive electrode active material are further improved.

[0080] The third component included in the grain boundary 20 may have a third phase, for example, a phase different from the phase contained in the primary particle. The third phase has, for example, a monoclinic crystal structure. Since the third component has a monoclinic crystal structure, lithium ions can move two-dimensionally in the grain boundary 20 including the third component, and thus the lithium ions are easily conducted in the core 100, for example, with reduced concentration polarization, resulting in an improvement in the cycle characteristics of the lithium battery. The third component may have, for example, a monoclinic crystal structure belonging to the C2 / m, C12 / c1, or C2 / c space group. Since the third component has a monoclinic crystal structure belonging to the C2 / m, C12 / c1, or C2 / c space group, the cycle characteristics and thermal stability of the lithium battery including the composite positive active material are improved.

[0081] The third metal included in the third component may be, for example, Zr, Al, Co, Mg, Mn, Si, Mo, Pd, Ti, Sn, Ir, Pt, or Ru. Since the third component includes the third metal, the charge and discharge characteristics of the lithium battery including the composite positive active material are improved.

[0082] In the composite positive electrode active material, the third component may include lithium, the third metal and oxygen. The third component may include, for example, about 1.7 moles to about 2.3 moles of lithium (based on 1 mole of the third component), about 0.7 moles to about 1.3 moles of the third metal (based on 1 mole of the third component), and about 2.7 to about 3.3 moles of oxygen (based on 1 mole of the third component). The third component may include, for example, about 1.8 moles to about 2.2 moles of lithium (based on 1 mole of the third component), about 0.8 moles to about 1.2 moles of the third metal (based on 1 mole of the third component), and about 2.8 to about 3.2 moles of oxygen (based on 1 mole of the third component). The third component may include, for example, about 1.9 moles to about 2.1 moles of lithium (based on 1 mole of the third component), about 0.9 moles to about 1.1 moles of the third metal (based on 1 mole of the third component), and about 2.9 to about 3.1 moles of oxygen (based on 1 mole of the third component).

[0083] The third component has a composition represented by, for example, the following Formula 3:

[0084] Formula 3

[0085] Li a M3 b O c

[0086] In formula 3,

[0087] M3 is Zr, Al, Co, Mg, Mn, Si, Mo, Pd, Ti, Sn, Ir, Pt, Ru, or a combination thereof, and satisfies the conditions of 1.9≤a≤2.1, 0.9≤b≤1.1 and 2.9≤a≤3.1.

[0088] Reference Figure 1B Due to the substantially straight shape of the primary particles, the grain boundary 20 in the core 100 of the composite positive active material 300 may have, for example, a substantially linear (linear) shape. Since the primary particles 10 adjacent to the grain boundary 20 have a polyhedral shape due to the inclusion of a nickel-lithium transition metal oxide having a layered crystal structure, the grain boundary 20 of the adjacent primary particles may have a linear or straight shape. In an embodiment, the grain boundary 20 may have, for example, a substantially curved or curved shape. The radius of curvature of the curve may be, for example, greater than 0 and equal to or less than 1 meter (m).

[0089] Reference Figure 1B The grain boundaries 20 of the composite positive active material 300 may be disposed, for example, in a direction 21 parallel to the surfaces of adjacent primary particles. In an embodiment, the direction in which the grain boundaries 20 are disposed may be different from the tangential direction 101 of the surface of the portion of the core 100 closest to the shell 200.

[0090] Reference Figure 1B , the core 100 of the composite positive active material 300 includes a first grain boundary 32 and a second grain boundary 33, the first grain boundary 32 and the second grain boundary 33 are directly disposed on the primary particle 30, and the first grain boundary 32 and the second grain boundary 33 intersect at an angle α determined by the shape of the primary particle 30. The angle α at which the first grain boundary 32 and the second grain boundary 33 intersect may be, for example, greater than 0° to less than about 180°, about 10° to about 170°, about 20° to about 160°, about 30° to about 150°, about 40° to about 140°, about 50° to about 130°, about 60° to about 120°, about 70° to about 110°, or about 80° to about 110°.

[0091] Reference Figure 1B , the core 100 of the composite positive active material 300 may include first and second grain boundaries 32 and 42 adjacent to the primary particles 30 and 40, respectively. The first and second grain boundaries 32 and 42 may be disposed in directions 31 and 41 parallel to the surfaces of the primary particles 30 and 40 adjacent thereto, respectively. The directions 31 and 41 of the first and second grain boundaries 32 and 42 are different from each other.

[0092] Reference Figure 1B , the core 100 of the composite positive active material 300 has an average grain boundary length of about 50nm to about 1000nm and an average grain boundary thickness of about 1nm to about 200nm. The length direction of the grain boundary is parallel to the surface of the primary particles 20, 30 and 40 adjacent thereto, and the thickness direction of the grain boundary is perpendicular to the surface of the primary particles 20, 30 and 40 adjacent thereto. The average grain boundary length may be, for example, in the range of about 50nm to about 950nm, about 100nm to about 900nm, about 150nm to about 800nm, or about 200nm to about 700nm. The average grain boundary thickness may be in the range of about 2nm to about 100nm, about 5nm to about 100nm, about 10nm to about 100nm, or about 20nm to about 100nm. Within the range of these average grain boundary lengths and average grain boundary thicknesses, a lithium battery including the composite positive active material may provide improved cycle characteristics and thermal stability. The average grain boundary length is the average value of the length d1 of the grain boundaries arranged in the first direction. The average grain boundary thickness is an average value of the thicknesses d2 of the grain boundaries arranged in the second direction.

[0093] The average particle size of the primary particles of the composite positive active material may be, for example, in the range of about 50 nm to about 500 nm, about 50 nm to about 450 nm, about 50 nm to about 400 nm, about 50 nm to about 350 nm, about 50 nm to about 300 nm, about 50 nm to about 250 nm, or about 50 nm to about 200 nm, but is not limited thereto. The average particle size of the primary particles of the composite positive active material may be adjusted as long as cycle characteristics and thermal stability are provided.

[0094] The average particle size of the core of the composite positive active material (which is a secondary particle in which the primary particles are gathered) may be, for example, about 1 micrometer (μm) to about 30 μm, about 2 μm to about 28 μm, about 4 μm to about 26 μm, about 6 μm to about 24 μm, about 8 μm to about 22 μm, about 10 μm to about 20 μm, about 12 μm to about 18 μm, about 12 μm to about 16 μm, or about 13 μm to about 15 μm, but is not limited thereto. The average particle size of the core may be adjusted as long as cycle characteristics and thermal stability are provided.

[0095] In an embodiment, the composite positive active material may further include the third component contained in the shell. In addition to the grain boundaries in the core, the third component may also be in the shell on the surface of the core. The third component of the shell has the same composition and the same crystal structure as the third component in the grain boundaries in the core, for example. The third component included in the shell may have, for example, a monoclinic crystal structure belonging to the C2 / m space group, the C12 / c1 space group, or the C2 / c space group. The third component included in the shell may have, for example, a composition represented by Formula 3 above.

[0096] In an embodiment, in the composite positive active material, the third metal may be doped on the lithium nickel transition metal oxide. Since the third metal is doped on the lithium nickel transition metal oxide, the structural stability of the lithium nickel transition metal oxide is improved.

[0097] The lithium nickel transition metal oxide of the composite positive electrode active material may include lithium, nickel, the third metal, a fourth metal and oxygen. The fourth metal refers to a metal other than lithium, nickel and the third metal.

[0098] The lithium nickel transition metal oxide of the composite cathode active material may include from about 0.1 mole to about 1.3 moles of lithium (based on 1 mole of the lithium nickel transition metal oxide), from about 0.7 mole to about 0.99 moles of nickel (based on 1 mole of the lithium nickel transition metal oxide), from about 0.0005 mole to about 0.01 mole of the third metal (based on 1 mole of the lithium nickel transition metal oxide), from about 0.01 mole to about 0.3 mole of the fourth metal (based on 1 mole of the lithium nickel transition metal oxide), and from about 1.7 moles to about 2.3 moles of oxygen (based on 1 mole of the lithium nickel transition metal oxide).

[0099] The lithium nickel transition metal oxide may be represented, for example, by Formula 4:

[0100] Formula 4

[0101] Li a M4O 2-α X α

[0102] Wherein in Formula 4, 0.9 ≤ a ≤ 1.2 and 0 ≤ α < 2,

[0103] M4 includes nickel, the third metal, and the fourth metal, the fourth metal is a Group 2 to Group 13 element other than nickel, the third metal, or a combination thereof, X is F, S, or P, and the amount of nickel in M4 is 70 mole% to less than 100 mole%. The lithium nickel transition metal oxide represented by Formula 4 may include a third metal, which may be introduced, for example, by doping.

[0104] The lithium nickel transition metal oxide may be represented, for example, by Formula 5:

[0105] Formula 5

[0106] Li a Ni b M5 c M6 d M7 e O 2-α X α

[0107] Wherein in Formula 5, 0.9 ≤ a ≤ 1.2, 0.7 < b < 1, 0 < c < 0.3, 0 < d < 0.3, 0 ≤ e < 0.1, b + c + d + e = 1, and 0 ≤ α < 2,

[0108] M5, M6, and M7 are different from each other and each is cobalt (Co), manganese (Mn), zirconium (Zr), aluminum (Al), rhenium (Re), vanadium (V), chromium (Cr), iron (Fe), boron (B), ruthenium (Ru), titanium (Ti), niobium (Nb), molybdenum (Mo), magnesium (Mg), or platinum (Pt), and X is F, S, or P. The lithium nickel transition metal oxide represented by Formula 5 may include the third metal that can be used for doping.

[0109] The lithium nickel transition metal oxide may be represented by, for example, one of Formulas 6 and 7:

[0110] Formula 6

[0111] Li a Ni b Co c Mn d M8 e O 2-α X α

[0112] Formula 7

[0113] Li a Ni b Co c Al d M8 e O 2-α X α

[0114] Wherein in Formulas 6 and 7, a, b, c, d, e, and α are each independently 0.9 ≤ a ≤ 1.2, 0.7 < b < 1, 0 < c < 0.1, 0 < d < 0.1, 0 ≤ e < 0.01, b + c + d + e = 1, and 0 ≤ α < 2.

[0115] M8 may be zirconium (Zr), aluminum (Al), vanadium (V), chromium (Cr), iron (Fe), rhenium (Re), boron (B), ruthenium (Ru), titanium (Ti), niobium (Nb), molybdenum (Mo), magnesium (Mg), or platinum (Pt), and X is F, S, or P. The lithium nickel transition metal oxide represented by one of Formulas 6 and 7 may include the third metal that can be used for doping.

[0116] The lithium nickel transition metal oxide of the composite positive electrode active material may include, for example, a first layered phase having a structure belonging to the C2 / m space group, a second layered phase having a structure belonging to the R-3m space group, or a combination thereof. The lithium nickel transition metal oxide may be, for example, a composite of the first layered phase and the second layered phase.

[0117] The lithium nickel transition metal oxide may include, for example, a first layered phase having a composition represented by Formula 8a and belonging to the C2 / m space group, and a second layered phase having a composition represented by Formula 8b and belonging to the R-3m space group.

[0118] Formula 8a

[0119] Li 2 MnO 3

[0120] Formula 8b

[0121] LiMO 2

[0122] wherein in Formula 8b,

[0123] M may include nickel (Ni) and cobalt (Co), manganese (Mn), vanadium (V), chromium (Cr), iron (Fe), zirconium (Zr), rhenium (Re), aluminum (Al), boron (B), ruthenium (Ru), titanium (Ti), niobium (Nb), molybdenum (Mo), magnesium (Mg), platinum (Pt), or a combination thereof. At least a portion of M is Ni. The amount of Ni in M may be about 70 mol% or greater, such as about 70 mol% to about 99 mol%. The second layered phase represented by Formula 8b may include, for example, the third metal for doping.

[0124] The lithium nickel transition metal oxide may be represented, for example, by Formula 8:

[0125] Formula 8

[0126] aLi 2 MnO 3 -(1-a)LiMO 2-α X α

[0127] wherein in Formula 8, 0 < a < 1 and 0 ≤ α < 2,

[0128] M may include nickel (Ni) and cobalt (Co), manganese (Mn), zirconium (Zr), aluminum (Al), rhenium (Re), vanadium (V), chromium (Cr), iron (Fe), boron (B), ruthenium (Ru), titanium (Ti), niobium (Nb), molybdenum (Mo), magnesium (Mg), platinum (Pt), or a combination thereof, and X is F, S or P. At least a portion of M is Ni. The amount of Ni in M may be about 70 mol% or greater, such as about 70 mol% to about 99 mol%. The lithium nickel transition metal oxide represented by Formula 8 may include the doped third metal.

[0129] Alternatively, the lithium nickel transition metal oxide may be, for example, a solid solution of a first layered phase having a structure belonging to the C2 / m space group. When the lithium nickel transition metal oxide has a solid solution structure belonging to the C2 / m space group, the lithium nickel transition metal oxide may be represented by Formulas 4a, 5a, 6a, and 7a, where each of Formulas 4a to 7a is the same as Formulas 4 to 7, except that 1.0 < a ≤ 1.2 and 0.8 ≤ b + c + d + e < 1.

[0130] The positive electrode according to the embodiment includes the above composite positive electrode active material. Since the positive electrode includes the above composite positive electrode active material, improved cycle characteristics and thermal stability can be provided.

[0131] The positive electrode is prepared, for example, by the following exemplary method, but the method for preparing the positive electrode is not necessarily limited thereto and can be adjusted as needed without undue experimentation.

[0132] The composite positive electrode active material, a conductive material, a binder, and a solvent are mixed to prepare a positive electrode active material composition. The positive electrode active material composition can be directly coated on an aluminum current collector and dried to form a positive electrode plate including a positive electrode active material layer. In an embodiment, the positive electrode active material composition is cast on a separate carrier, and then the film is peeled off from the carrier and laminated on an aluminum current collector to prepare a positive electrode plate including a positive electrode active material layer.

[0133] Examples of the conductive material are: carbon black, graphite particles, natural graphite, artificial graphite, acetylene black, Ketjen black, carbon fiber; carbon nanotubes; copper, nickel, aluminum, or silver, in the form of metal powder, metal fiber, or metal tube; and conductive polymers such as polyphenylene derivatives, but the conductive material is not limited thereto and can be any suitable conductive material.

[0134] Examples of the binder are vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polytetrafluoroethylene (“PTFE”), mixtures of these polymers, and styrene-butadiene rubber-based polymers. As the solvent usable herein, N-methylpyrrolidone (“NMP”), acetone, water, etc. can be used. However, the solvent is not limited thereto and can be any suitable material.

[0135] The positive electrode active material composition may further include a plasticizer or a pore former to form pores in the electrode plate.

[0136] The amounts of the composite positive electrode active material, the conductive material, the binder, and the solvent for the positive electrode are at the same levels as those typically used in secondary batteries. Depending on the purpose and structure of the secondary battery, at least one of the conductive material, the binder, and the solvent may not be used.

[0137] In an embodiment, the positive electrode may further include another composite positive electrode active material in addition to the composite positive electrode active material.

[0138] The additional positive electrode active material may include a lithium-containing metal oxide. Such a lithium-containing metal oxide may be at least one composite oxide including lithium and cobalt, manganese, nickel, or a combination thereof, and the additional positive electrode active material may be represented as follows: Li a A 1-b B' b D 2 (where 0.90≤a≤1, and 0≤b≤0.5); Li a E 1-b B' b O 2-c D c (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05); LiE 2-b B' b O 4-c D c (where 0≤b≤0.5, 0≤c≤0.05); Li a Ni 1-b-c Co b B' c D α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, 0<α≤2); Li a Ni 1-b-c Co b B' c O 2-α F' α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, 0<α<2); Li a Ni 1-b-c Co b B' c O 2-α F' 2 (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, 0<α<2); Li a Ni 1-b-c Mn b B' c D α (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, 0<α≤2); Li a Ni 1-b-c Mn b B' c O 2-α F' α(where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, 0<α<2); Li a Ni 1-b-c Mn b B' c O 2-α F' 2 (where 0.90≤a≤1, 0≤b≤0.5, 0≤c≤0.05, 0<α<2); Li a Ni b E c G d O 2 (where 0.90≤a≤1, 0≤b≤0.9, 0≤c≤0.5, 0.001≤d≤0.1); Li a Ni b Co c Mn d G e O 2 (where 0.90≤a≤1, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, 0.001≤e≤0.1); Li a NeG b O 2 (where 0.90≤a≤1, 0.001≤b≤0.1); Li a CoG b O 2 (where 0.90≤a≤1, 0.001≤b≤0.1); Li a MnG b O 2 (where 0.90≤a≤1, 0.001≤b≤0.1); Li a Mn 2 G b O 4 (where 0.90≤a≤1, 0.001≤b≤0.1); QO 2 ;QS 2 ;LiQS 2 ; V 2 O 5 ;LiV 2 O 5 ;LiI'O 2 ;LiNiVO 4 ;Li (3-f) J 2 (PO 4 ) 3 (0≤f≤2);Li (3-f) Fe 2 (PO 4 ) 3 (0≤f≤2); or LiFePO4 .

[0139] In the above formula, A is Ni, Co, Mn, or a combination thereof; B' is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element, or a combination thereof; D is O, F, S, P, or a combination thereof; E is Co, Mn, or a combination thereof; F' is F, S, P, or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or a combination thereof; Q is Ti, Mo, Mn, or a combination thereof; I' is Cr, V, Fe, Sc, Y, or a combination thereof; and J is V, Cr, Mn, Co, Ni, Cu, or a combination thereof.

[0140] These compounds can be used in the case of having a coating layer thereon, and a mixture of a compound having a coating layer thereon and a compound having no coating layer thereon can be used. The coating layer may include an oxide of a coating element, a hydroxide of a coating element, an oxyhydroxide of a coating element, an oxycarbonate of a coating element, or a hydroxycarbonate of a coating element. The compounds constituting these coating layers may be amorphous or crystalline. As the coating element included in the coating layer, Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a combination thereof may be used. The method for forming the coating layer may be selected as long as the method does not adversely affect the physical properties of the positive electrode active material. Coating methods include, for example, spraying, impregnation, etc. The details of these coating methods are well understood by those skilled in the art, and therefore a detailed description thereof will be omitted.

[0141] The positive electrode may include, for example, the above-mentioned composite positive electrode active material, and an olivine-based positive electrode active material.

[0142] The olivine-based positive active material may be represented by, for example, Formula 9 below.

[0143] Formula 9

[0144] Li x M8 y M9 z PO 4-α X α

[0145] Wherein in Formula 9, 0.90≤x≤1.1, 0≤y≤0.9, 0≤z≤0.5, 1-yz≥0, and 0≤α≤2, M8 is Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Al, Mg, Zr, B, or a combination thereof, M9 is Mg, Ca, Sr, Ba, Ti, Zr, Nb, Mo, W, Zn, Al, Si, Ni, Mn, Cr, Fe, Mg, Sr, V, a rare earth element, or a combination thereof, and X is F, S, or P. The olivine-based positive active material may be, for example, LiFePO 4 、LiNiPO 4 、LiMnPO 4 , or LiCoPO 4 .

[0146] The amount of the olivine-based positive active material included in the positive electrode may be, for example, about 10 weight percent (wt%) or less, about 9 weight % or less, about 8 weight % or less, about 7 weight % or less, about 6 weight % or less, or about 5 weight % or less, based on the total weight of the positive active material. The amount of the olivine-based positive active material included in the positive electrode may be, for example, in the range of about 1 to about 10 weight %, about 1 weight % to about 9 weight %, about 1 weight % to about 8 weight %, about 1 weight % to about 7 weight %, about 1 weight % to about 6 weight % or about 1 weight % to about 5 weight %, based on the total weight of the positive active material. The amount of the olivine-based positive active material included in the positive electrode may be, for example, about 1 part by weight to about 10 parts by weight, about 1 part by weight to about 9 parts by weight, about 1 part by weight to about 8 parts by weight, about 1 part by weight to about 7 parts by weight, about 1 part by weight to about 6 parts by weight, or about 1 part by weight to about 5 parts by weight, based on 100 parts by weight of the composite positive active material. Since the positive electrode includes such an amount range of the olivine-based positive electrode active material, the cycle characteristics and mix density of the lithium battery may be improved.

[0147] Embodiments provide a lithium battery including a positive electrode including the composite positive electrode active material.

[0148] Since the lithium battery includes the positive electrode including the composite positive electrode active material, improved cycle characteristics and thermal stability may be provided.

[0149] For example, the lithium battery is prepared by the following example method, but the preparation method is not limited thereto and can be adjusted as needed.

[0150] First, a positive electrode is manufactured according to the above-mentioned positive electrode manufacturing method.

[0151] Next, a negative electrode is manufactured as follows. The negative electrode is manufactured in substantially the same manner as that for manufacturing the positive electrode, except that, for example, a negative electrode active material is used instead of the composite positive electrode active material. The conductive material, binder, and solvent constituting the negative electrode active material composition can be the same as those used for manufacturing the positive electrode.

[0152] For example, the negative electrode active material, the conductive material, the binder, and the solvent are mixed to prepare a negative electrode active material composition, which is then directly coated on a copper current collector to complete the preparation of the negative electrode plate. In an embodiment, the negative electrode active material composition is cast on a separate carrier, and the negative electrode active material film peeled off from the carrier is laminated on the copper current collector, thereby completing the preparation of the negative electrode plate.

[0153] The negative electrode active material can be any suitable material that can be used as a negative electrode active material for a lithium battery. The negative electrode active material can be lithium metal, a metal capable of alloying with lithium, a transition metal oxide, a non-transition metal oxide, a carbonaceous material, or a combination thereof.

[0154] In an embodiment, the metal capable of alloying with lithium can be Si, Sn, Al, Ge, Pb, Bi, Sb, a Si-Y' alloy (where Y' is an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a Group 15 element, a Group 16 element, a transition metal, a rare earth element, or a combined element thereof and is not Si), or a Sn-Y" alloy (where Y" is an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a Group 15 element, a Group 16 element, a transition metal, a rare earth element, or a combined element thereof and is not Sn). The element Y' or Y" can be Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, or a combination thereof.

[0155] In an embodiment, the transition metal oxide can be lithium titanium oxide, vanadium oxide, lithium vanadium oxide, etc.

[0156] In an embodiment, the non-transition metal oxide can be SnO 2 、SiO x (0 < x < 2), etc.

[0157] In an embodiment, the carbonaceous material may be crystalline carbon, amorphous carbon or a mixture thereof. In an embodiment, the crystalline carbon may be natural or artificial graphite, which is non-shaped, plate-like, flaky, spherical or fibrous. In an embodiment, the amorphous carbon may be soft carbon (cold calcined carbon) or hard carbon, mesophase pitch carbonization product, calcined coke, etc.

[0158] The amounts of the negative electrode active material, the conductive material, the binder and the solvent used in the negative electrode are the same levels as those typically used in secondary batteries. Depending on the purpose and structure of the secondary battery, at least one of the conductive material, the binder and the solvent may not be used.

[0159] Next, a separator to be inserted between the positive electrode and the negative electrode is prepared.

[0160] The separator may be any suitable separator typically used in secondary batteries such as lithium batteries. The material used to form the separator may be a material having low resistance to ion migration of the electrolyte and having excellent electrolyte solution retention capacity. In an embodiment, the separator forming material may be glass fiber, polyester, Teflon, TM , polyethylene, polypropylene, polytetrafluoroethylene ("PTFE"), or a combination thereof, each of which may be in the form of a nonwoven fabric or a woven fabric. In an embodiment, the separator for a lithium ion battery may be a windable separator formed of polyethylene or polypropylene, and the separator for a lithium ion polymer battery may be a separator having excellent organic electrolyte retention capability.

[0161] The separator is prepared, for example, by the following exemplary method, but the preparation method of the separator is not necessarily limited thereto and is adjusted according to required conditions.

[0162] First, a separator composition is prepared by mixing a polymer resin, a filler and a solvent. The separator composition can be directly coated on a positive electrode plate or a negative electrode plate to form the separator. In some embodiments, the separator composition can be cast and dried on a support, and the separator film peeled off from the support is laminated on an electrode to complete the preparation of the separator.

[0163] The polymer used in preparing the separator may not be particularly limited, and any suitable material that can be used as a binder for an electrode plate may be used. Examples of the polymer resin are vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride ("PVDF"), polyacrylonitrile, polymethyl methacrylate, and mixtures thereof.

[0164] Next, an electrolyte is prepared.

[0165] The electrolyte may be, for example, an organic electrolyte solution prepared by dissolving a lithium salt in an organic solvent.

[0166] The organic solvent may be any suitable material that can be used as an organic solvent. Examples of the organic solvent are propylene carbonate, ethylene carbonate, fluoroethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, dibutyl carbonate, benzonitrile, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, γ-butyrolactone, dioxolane, 4-methyldioxolane, N,N-dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dioxane, 1,2-dimethoxyethane, cyclopentane, dichloroethane, chlorobenzene, nitrobenzene, diethylene glycol, dimethyl ether, or a combination thereof.

[0167] The lithium salt may be any suitable material that can be used as a lithium salt. The lithium salt may be, for example, LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiClO 4 、LiCF 3 SO 3 、Li(CF 3 SO 2 ) 2 N, LiC 4 F 9 SO 3 、LiAlO 2 、LiAlCl 4 , where x and y are natural numbers LiN(C x F 2x+1 SO 2 )(C y F 2y+1 SO 2 ), LiCl, LiI, or a combination thereof.

[0168] In an embodiment, the electrolyte may be a solid electrolyte. The solid electrolyte may be boron oxide, lithium oxynitride, etc., but is not limited thereto. The solid electrolyte may be any suitable material that can be used as a solid electrolyte. The solid electrolyte may be formed on the negative electrode by, for example, sputtering, or a separate solid electrolyte sheet may be stacked on the negative electrode.

[0169] like Figure 5 As shown in FIG. 1 , a lithium battery 1 includes a positive electrode 3, a negative electrode 2, and a separator 4. The positive electrode 3, the negative electrode 2, and the separator 4 are wound and folded and housed in a battery case 5. An organic electrolyte solution is injected into the battery case 5 and sealed with a cap assembly 6 to complete the manufacture of the lithium battery 1. The battery case 5 is cylindrical, but is not necessarily limited to this shape, and may have, for example, a rectangular shape, a thin film shape, etc.

[0170] The pouch-type lithium battery includes one or more battery assemblies. The battery assembly is formed by placing a separator between the positive electrode and the negative electrode. The battery assembly is stacked in a double-cell structure, impregnated with an organic electrolyte solution, and contained and sealed in a bag to complete the manufacture of the pouch-type lithium battery. In an embodiment, a plurality of battery assemblies can be stacked to form a battery pack, which is used in all devices requiring high capacity and high output. For example, the battery pack can be used in notebooks, smart phones, electric vehicles, etc.

[0171] Because lithium batteries have excellent life characteristics and high rate characteristics, the lithium batteries can be used, for example, in electric vehicles ("EV"). For example, the lithium batteries can be used in hybrid vehicles such as plug-in hybrid electric vehicles ("PHEV"). In embodiments, the lithium batteries can be used in fields where a large amount of energy storage is required. In embodiments, the lithium batteries can be used in electric bicycles, power tools, etc.

[0172] An embodiment provides a method for preparing the composite positive active material, the method comprising: preparing a lithium nickel transition metal oxide; preparing a mixed composition by sequentially or simultaneously adding a first metal precursor and a second metal precursor to the lithium nickel transition metal oxide; and drying the mixed composition and heat treating it at a temperature of about 400°C to about 1000°C in an oxidizing atmosphere.

[0173] Sequentially adding a first metal precursor and a second metal precursor to the lithium nickel transition metal oxide to prepare a mixed composition may include, for example, mixing the lithium nickel transition metal oxide and the first metal precursor to prepare a first composition of the lithium nickel transition metal oxide; and mixing the first composition of the lithium nickel transition metal oxide and the second metal precursor to prepare a mixed composition of the lithium nickel transition metal oxide.

[0174] Adding a first metal precursor and a second metal precursor simultaneously to the lithium nickel transition metal oxide to prepare a mixed composition may include, for example, mixing the lithium nickel transition metal oxide with the first metal precursor and the second metal precursor to prepare the mixed composition of the lithium nickel transition metal oxide.

[0175] The preparation of the mixed composition can be carried out by a wet method such as using a solvent. The first composition and the mixed composition can each include a solvent capable of dissolving the first metal precursor and the second metal precursor. In this regard, the solvent is not limited and can be any suitable material that can be used as a solvent. The solvent can be, for example, distilled water. For example, the first metal precursor and the second metal precursor can each be used in an aqueous form.

[0176] The first metal precursor may be a nitrate, an oxychloride, an oxynitrate, etc. of the first metal, but is not limited thereto. The first metal precursor may be any suitable material that can be used as a dissociated salt containing the first metal. For example, the first metal precursor may be Co(NO 3 ) 2 6H 2 O、Mg(NO 3 ) 2 6H 2 O, etc. In the first composition, the hydroxide of the first metal is precipitated on the surface of the lithium nickel transition metal oxide. The hydroxide of the first metal may be, for example, Co(OH) 2 Mg(OH) 2 wait.

[0177] The second metal precursor may be a nitrate, an oxychloride, an oxynitrate, etc. of the second metal, but is not limited thereto. The second metal precursor may be any suitable material that can be used as a dissociated salt containing the second metal. For example, the second metal precursor may be Ce(NO 3 ) 2 6H 2 O、CeCl 3 、CeCl 3 7H 2 O、Ce(SO 4 ) 2 、Ce(SO 4 ) 2 ·4H 2 O.Ce 2 (SO 4 ) 3 、Ce 2 (SO 4 ) 3 8H 2 O、Ce(NH 4 ) 2 (NO 3 ) 6 、Ce(NH 4 ) 4 (SO 4 ) 4 ·2H 2 O、Ce(C 5 H 7 O 2 ) 3 ·xH 2 O, or Ce(CH 3 CO 2 ) 3 ·xH 2 O. "xH 2O" refers to a hydrate, wherein the water content may vary depending on, for example, humidity.

[0178] The oxidizing atmosphere is an atmosphere containing oxygen or air. The oxidizing atmosphere contains oxygen, air, or a combination thereof, such as air with an increased oxygen content.

[0179] The amount of the first metal precursor in the first composition or the mixed composition may be about 30 parts by weight or less, such as about 1 to about 25 parts by weight; about 20 parts by weight or less, such as about 2 to about 15 parts by weight; or about 10 parts by weight or less, such as about 3 to about 9 parts by weight, based on 100 parts by weight of the lithium nickel transition metal oxide. The amount of the solvent in the first composition or the mixed composition may be about 300 parts by weight or less, such as about 1 to about 250 parts by weight; about 200 parts by weight or less, such as about 5 to about 150 parts by weight; or about 100 parts by weight or less, such as about 10 to about 75 parts by weight, based on 100 parts by weight of the lithium nickel transition metal oxide. The amount of the second metal precursor in the mixed composition may be about 30 parts by weight or less, such as about 1 to about 25 parts by weight; about 20 parts by weight or less, such as about 2 to about 15 parts by weight; or about 10 parts by weight or less, such as about 3 to about 9 parts by weight, based on 100 parts by weight of the lithium nickel transition metal oxide. The amount of the solvent in the mixed composition may be about 300 parts by weight or less, about 200 parts by weight or less, such as about 1 to about 250 parts by weight; or about 100 parts by weight or less, such as about 10 to about 75 parts by weight, based on 100 parts by weight of the lithium nickel transition metal oxide.

[0180] The heat treatment may be performed at a temperature of, for example, about 400°C to about 1000°C, about 500°C to about 900°C, about 600°C to about 800°C, or about 700°C to about 750°C. The heat treatment time may be, for example, in the range of about 3 hours to about 20 hours, about 3 hours to about 15 hours, about 3 hours to about 10 hours, about 3 hours to about 7 hours, or about 4 hours to about 6 hours. The heating rate to reach the temperature at which the heat treatment is performed may be, for example, about 1°C / minute (°C / min) to about 10°C / minute. Since the heat treatment temperature, the heat treatment time, and the heating rate have these ranges, a shell including a first layer on the core and a second layer on the first layer may be formed on the core.

[0181] In the method for preparing the composite positive electrode active material, the preparation of the lithium nickel transition metal oxide includes: mixing a precursor for the lithium nickel transition metal oxide and a third metal precursor to prepare a mixture; and heat treating the mixture at a temperature of about 400°C to about 1000°C in an oxidizing atmosphere to prepare the lithium nickel transition metal oxide.

[0182] The preparation of the mixture can be carried out by, for example, a dry method without using a solvent. The mixture can be, for example, a dry powder prepared by mixing a powder of a lithium nickel transition metal oxide precursor and a third metal precursor powder. In an embodiment, the preparation of the mixture can be carried out by, for example, a wet method using a solvent. The mixture may include a solvent capable of dissolving a precursor of the lithium nickel transition metal oxide and the third metal precursor. In this regard, the solvent is not limited and may be any suitable material that can be used as a solvent. The solvent may be, for example, distilled water. Due to the wet method, the third component containing the third metal can be included at a relatively high concentration at the grain boundaries between primary particles.

[0183] The oxidizing atmosphere is an atmosphere containing oxygen or air. The oxidizing atmosphere contains oxygen, air, or a combination thereof, such as air with an increased oxygen content.

[0184] The third metal precursor may be, for example, an oxide or hydroxide of the third metal, but is not limited thereto. In this regard, the third metal precursor may be any suitable material containing the third metal. For example, the third metal precursor may be, for example, ZrO 2 or Al 2 O 3 .

[0185] The amount of the third metal precursor in the mixture may be about 30 parts by weight or less, such as about 1 to about 25 parts by weight; about 20 parts by weight or less, such as about 2 to about 15 parts by weight; or 10 parts by weight or less, such as about 3 to about 9 parts by weight, based on 100 parts by weight of the lithium nickel transition metal oxide precursor.

[0186] The heat treatment may be performed at, for example, about 400°C to about 1000°C, about 500°C to about 900°C, about 600°C to about 800°C, or about 700°C to about 750°C. The heat treatment time may be, for example, in the range of about 3 hours to about 20 hours, about 3 hours to about 15 hours, about 3 hours to about 10 hours, about 3 hours to about 7 hours, or about 4 hours to about 6 hours. The heating rate to reach the temperature for performing the heat treatment may be, for example, about 1°C / minute to about 10°C / minute. When the heat treatment temperature, the heat treatment time, and the heating rate are within these ranges, the third component including the third metal is formed at the grain boundaries between the primary particles, and the third metal is doped on the lithium nickel transition metal oxide.

[0187] The embodiments of the present disclosure will be described in more detail with reference to the following examples and comparative examples. These examples are provided herein for illustrative purposes only and do not limit the scope of the present disclosure.

[0188] Example

[0189] Preparation of composite positive electrode active materials

[0190] Example 1: Ni88+Al-Zr doping, Li 2 ZrO 3 Grain boundary coating + Co:Ce = 0.5 weight percent (wt%): 1.5 wt%, two-layer coating

[0191] Core preparation

[0192] Zirconium oxide (ZrO 2 ) and aluminum oxide (Al 2 O 3 ), Ni as a precursor of lithium nickel transition metal oxide 0.88 Co 0.08 Mn 0.04 (OH) 2 (Lanzhou JinTong energy storage power new material Co., Ltd., China) and LiOH or LiOH·H as lithium precursor 2 O was mixed in a molar ratio of 0.003:0.0005:0.996:1.09 to prepare a mixture. The mixture was placed in a furnace and subjected to a preliminary heat treatment at a temperature of 750° C. for 5 hours while flowing oxygen to prepare a core.

[0193] As a result of the preliminary heat treatment, Al- and Zr-doped Li as lithium nickel transition metal oxide is obtained. 1.09 (Ni 0.88 Co 0.08 Mn 0.04 ) 1-x-y Al x Zr y O 2 (x=0.001, y=0.003) core.

[0194] In addition, Li having a monoclinic crystal structure is formed on the surface of the core and in the grain boundaries between the plurality of primary particles. 2 ZrO 3 Wrap.

[0195] Shell preparation

[0196] The Co(NO) in the first layer of the composite positive electrode active material is prepared in this way. 3 ) 2 6H 2 O precursor, so that the amount of Co is 0.5 parts by weight, based on 100 parts by weight of the lithium nickel transition metal oxide, and then Co(NO3 ) 2 6H 2 The O precursor was added to 10 parts by weight of distilled water and stirred at room temperature (25° C.) for 1 minute to prepare a first aqueous solution.

[0197] The Ce(NO) in the second layer of the composite positive electrode active material is prepared in this way. 3 ) 2 6H 2 O precursor, so that the amount of Ce is 1.5 parts by weight, based on 100 parts by weight of the lithium nickel transition metal oxide, and then Ce (NO 3 ) 2 6H 2 The O precursor was added to 10 parts by weight of distilled water and stirred at room temperature (25° C.) for 1 minute to prepare a second aqueous solution.

[0198] 100 parts by weight of Li 1.09 (Ni 0.88 Co 0.08 Mn 0.04 ) 1-x-y Al x Zr y O 2 The (x=0.001, y=0.003) core powder was added to 90 parts by weight of distilled water to prepare a third aqueous solution, and while stirring at room temperature for 10 minutes, the first aqueous solution and the second aqueous solution were sequentially added in this order to prepare a mixture.

[0199] The mixture was dried in an oven at a temperature of 150° C. for 15 hours to prepare a dried product.

[0200] The dried product was placed in a furnace and subjected to heat treatment at a temperature of 720° C. for 5 hours while flowing oxygen to prepare a composite positive active material.

[0201] In Li 1.09 (Ni 0.88 Co 0.08 Mn 0.04 ) 1-x-y Al x Zr y O 2 The surface of the core (x=0.001, y=0.003) is formed with LiCoO 2 and Co 3 O 4 A first layer including CeO is formed on the first layer 2 The second layer.

[0202] The amount of Co in the first layer was 0.5 parts by weight based on 100 parts by weight of the lithium nickel transition metal oxide, and the amount of Ce in the second layer was 1.5 parts by weight based on 100 parts by weight of the lithium nickel transition metal oxide.

[0203] Example 2: Ni88+Al-Zr doping, Li 2 ZrO 3 Grain boundary coating + Co:Ce = 0.75 wt%: 1.5 wt%, two-layer coating

[0204] A composite positive electrode active material was prepared in the same manner as in Example 1, except that Co(NO 3 ) 2 6H 2 The amount of the O precursor is such that the amount of Co in the first layer of the composite positive electrode active material is 0.75 parts by weight based on 100 parts by weight of the lithium nickel transition metal oxide.

[0205] The amount of Co in the first layer was 0.75 parts by weight based on 100 parts by weight of the lithium nickel transition metal oxide, and the amount of Ce in the second layer was 1.5 parts by weight based on 100 parts by weight of the lithium nickel transition metal oxide.

[0206] Example 3: Ni88+Al-Zr doping, Li 2 ZrO 3 Grain boundary coating + Co:Ce = 0.5 wt %: 1.5 wt %, one layer of composite coating

[0207] A composite positive active material was prepared in the same manner as in Example 1, except that in preparing the shell, the first aqueous solution and the second aqueous solution were simultaneously added to the third aqueous solution.

[0208] In Li 1.09 (Ni 0.88 Co 0.08 Mn 0.04 ) 1-x-y Al x Zr y O 2 (x=0.001, y=0.003) A composite layer including Co and Ce is formed on the surface of the core.

[0209] The amount of Co in the first layer was 0.5 parts by weight based on 100 parts by weight of the lithium nickel transition metal oxide, and the amount of Ce in the first layer was 1.5 parts by weight based on 100 parts by weight of the lithium nickel transition metal oxide.

[0210] Example 4: Ni88+Al doping (without Zr)+Co:Ce=0.5 wt %:1.5 wt %, two-layer coating

[0211] A composite positive electrode active material was prepared in the same manner as in Example 1, except that in preparing the core, as the third metal precursor, aluminum oxide (Al 2 O 3 ) and does not use zirconium oxide (ZrO 2 ).

[0212] As a result of the preliminary heat treatment, Al-doped Li 1.09 (Ni 0.88 Co 0.08 Mn 0.04 ) 1-x Al x O 2 (x=0.001) core.

[0213] The amount of Co in the first layer was 0.5 parts by weight based on 100 parts by weight of the lithium nickel transition metal oxide, and the amount of Ce in the second layer was 1.5 parts by weight based on 100 parts by weight of the lithium nickel transition metal oxide.

[0214] Comparative Example 1: Ni88 Core

[0215] The Li prepared by the preliminary heat treatment in Example 1 was used. 1.09 (Ni 0.88 Co 0.08 Mn 0.04 ) 1-x- y Al x Zr y O 2 (x=0.001, y=0.003) core powder.

[0216] Comparative Example 2: Ni88 core + washing

[0217] 100 parts by weight of Li prepared during the preliminary heat treatment of Example 1 1.09 (Ni 0.88 Co 0.08 Mn 0.04 ) 1-x-y Al x Zr y O 2 (x=0.001, y=0.003) The core powder was added to 90 parts by weight of distilled water. After stirring, the precipitate was filtered and separated to remove residual lithium. This washing process was performed once.

[0218] The separated precipitate was dried in an oven at a temperature of 150° C. for 15 hours to prepare a dried product.

[0219] The dried product was placed in a furnace and subjected to heat treatment at a temperature of 720° C. for 5 hours while flowing oxygen to prepare a composite positive active material.

[0220] Comparative Example 3: Ni88+Al-Zr doping, Li 2 ZrO 3 Grain boundary coating + Co:Ce = 0.75 wt%: 0.0 wt%, Co coating only

[0221] A composite positive electrode active material was prepared in the same manner as in Example 1, except that in preparing the shell, Co(NO 3 ) 2 6H 2 O precursor, so that the amount of Co in the first layer of the composite positive electrode active material is 0.75 parts by weight, based on 100 parts by weight of the lithium nickel transition metal oxide, and no Ce (NO 3 ) 2 6H 2 O in a second aqueous solution.

[0222] In Li 1.09 (Ni 0.88 Co 0.08 Mn 0.04 ) 1-x-y Al x Zr y O 2 (x=0.001, y=0.003) The surface of the core contains LiCoO 2 and Co 3 O 4 The second layer is not formed.

[0223] The amount of Co in the first layer was 0.75 parts by weight based on 100 parts by weight of the lithium nickel transition metal oxide.

[0224] Comparative Example 4: Ni88+Al-Zr doping, Li 2 ZrO 3 Grain boundary coating + Co:Ce = 0 wt%: 1.5 wt%, Ce coating only

[0225] A composite positive active material was prepared in the same manner as in Example 1, except that in preparing the shell, the shell containing Co(NO 3 ) 2 6H 2 O first aqueous solution.

[0226] In Li 1.09 (Ni 0.88 Co 0.08 Mn 0.04 ) 1-x-y Al x Zr y O 2 (x=0.001, y=0.003) The surface of the core is formed with CeO 2 The second layer is not formed.

[0227] The amount of Ce in the first layer was 1.5 parts by weight based on 100 parts by weight of the lithium nickel transition metal oxide.

[0228] Preparation of lithium battery (half-cell)

[0229] Example 5

[0230] Preparation of positive electrode

[0231] The composite positive active material of Example 1, a carbon conductive material (Denka Black) and polyvinylidene fluoride ("PVdF") were mixed in a weight ratio of 92:4:4 to prepare a mixture, and then the mixture was mixed with N-methylpyrrolidone ("NMP") in an agate mortar to prepare a slurry. The slurry was bar-coated on an aluminum current collector having a thickness of 15 micrometers (μm), dried at room temperature, dried again under vacuum at a temperature of 120° C., and rolled and punched to produce a positive electrode plate having a thickness of 55 μm.

[0232] Preparation of coin cell batteries

[0233] A coin cell battery was manufactured by using the positive electrode plate prepared as described above, a counter electrode including lithium metal, a polytetrafluoroethylene ("PTFE") separator, and a 1.15 M LiPF dissolved in ethylene carbonate ("EC"), ethyl methyl carbonate ("EMC"), and dimethyl carbonate ("DMC") (3:4:3 volume ratio). 6 of electrolytes.

[0234] Embodiment 6-8

[0235] A coin cell was manufactured in the same manner as in Example 5, except that the composite positive active material of Examples 2 to 4 was used instead of the composite positive active material prepared in Example 1.

[0236] Example 9: LiFePO 4 Addition of (LFP)

[0237] A coin cell battery was manufactured in the same manner as in Example 5, except that 5 parts by weight of LiFePO4 Added to 100 parts by weight of the composite positive electrode active material prepared in Example 1.

[0238] Comparative Examples 5-8

[0239] A coin cell was manufactured in the same manner as in Example 5, except that the composite positive active materials of Comparative Examples 1 to 4 were used instead of the composite positive active material prepared in Example 1.

[0240] Manufacturing of lithium batteries (full cell batteries)

[0241] Example 10

[0242] Preparation of positive electrode

[0243] The composite positive active material of Example 1, a carbon conductive material (Denka Black) and polyvinylidene fluoride ("PVdF") were mixed in a weight ratio of 92:4:4 to prepare a mixture, and then the mixture was mixed with N-methylpyrrolidone ("NMP") in an agate mortar to prepare a positive active material slurry. The slurry was bar-coated on an aluminum current collector having a thickness of 15 μm, dried at room temperature, dried again under vacuum at a temperature of 120°C, and rolled and punched to produce a positive plate having a thickness of 55 μm.

[0244] Preparation of negative electrode

[0245] Graphite particles having an average particle size of 25 μm, a styrene-butadiene rubber (“SBR”) binder (ZEON) and carboxymethyl cellulose (“CMC”, NIPPON A&L) were mixed at a weight ratio of 97:1.5:1.5 and then the mixture was added to distilled water, followed by stirring for 60 minutes, thereby completing the preparation of a negative electrode active material slurry. The negative electrode active material slurry was coated on a copper current collector having a thickness of 10 μm by using a doctor blade, dried in a hot air dryer at 100° C. for 0.5 hours, dried again at a temperature of 120° C. in a vacuum for 4 hours, and rolled and punched to manufacture a negative electrode plate having a thickness of 65 μm.

[0246] Preparation of coin cell batteries

[0247] A coin cell battery was manufactured by using the positive and negative plates prepared as described above, a PTFE separator, and a 1.15 M LiPF dissolved in ethylene carbonate ("EC"), ethyl methyl carbonate ("EMC"), and dimethyl carbonate ("DMC") (3:4:3 volume ratio). 6 of electrolytes.

[0248] Examples 11-13

[0249] A coin cell was manufactured in the same manner as in Example 10, except that the composite positive active material of Examples 2-4 was used instead of the composite positive active material prepared in Example 1.

[0250] Example 14: Addition of LFP

[0251] A coin cell was manufactured in the same manner as in Example 10, except that 5 parts by weight of LiFePO 4 Added to 100 parts by weight of the composite positive electrode active material prepared in Example 1.

[0252] Comparative Examples 9-12

[0253] A coin cell was manufactured in the same manner as in Example 10, except that the composite positive active materials of Comparative Examples 1 to 4 were used instead of the composite positive active material prepared in Example 1.

[0254] Comparative Example 13 (Ce 0.29 wt%)

[0255] A lithium battery (full unit cell) was prepared in the same manner as in Example 10, except that the composite positive electrode active material of Comparative Example 4 was used instead of the composite positive electrode active material of Example 1, and in preparing the shell, Ce(NO 3 ) 2 6H 2 O precursor, such that the amount of Ce in the first layer of the composite positive electrode active material is 0.29 parts by weight, based on 100 parts by weight of the lithium nickel transition metal oxide

[0256] Evaluation Example 1: X-ray Diffraction ("XRD") Spectrum Evaluation

[0257] The XRD spectra of the composite positive electrode active materials of Examples 1-2 and Comparative Examples 3-4 were measured. The results are shown in Figure 2A and 2B In. XRD spectra were measured by Cu Kα irradiation.

[0258] Reference Figure 2A , the XRD spectrum of the composite positive electrode active material of Comparative Example 3 including the coating layer containing the Co component only shows a peak corresponding to a phase having a layered crystal structure belonging to the space group R-3m. Therefore, it is confirmed that the Co-containing component included in the coating layer has a layered crystal structure belonging to the space group R-3m.

[0259] Reference Figure 2AThe XRD spectra of the composite positive electrode active materials of Comparative Example 4 in which the coating layer includes a Ce-containing component alone and Examples 1 and 2 in which the coating layer includes a Ce-containing component and a Co-containing component show, in addition to the peak corresponding to the layered crystal structure, a peak at a diffraction angle (2θ) of 27° to 30°, a peak at a diffraction angle (2θ) of 32° to 35°, a peak at a diffraction angle (2θ) of 46° to 48°, and a peak at a diffraction angle (2θ) of 56° to 58°. Therefore, it is confirmed that a second phase different from the first phase structure included in the Co-containing component is additionally formed. From Figure 2A It is confirmed that the Ce-containing component included in the cladding layer has a second phase having a fluorite crystal structure belonging to the Fm-3m space group.

[0260] The Rietveld refinement analysis confirmed that the Co-containing component has LiCoO 2 Phase, Co 3 O 4 phase, and the Ce-containing component has CeO 2 Mutually.

[0261] Reference as Figure 2A A partial enlarged view of Figure 2B , confirming that the composite positive electrode active materials of Comparative Example 3 and Examples 1-2 in which the coating layer has a Co-containing component additionally have a 2 Therefore, it is confirmed that the coating layer has LiCoO 2 The composite positive electrode active material of Comparative Example 4 does not have a phase corresponding to LiCoO 2 Phase peak.

[0262] Evaluation Example 2: Evaluation of the surface and internal composition of the core

[0263] Figures 3A-3E Scanning electron microscope (SEM) images showing the surfaces of the composite positive active materials of Comparative Examples 1, 3 and 4 and Examples 1 and 2. The surface composition was analyzed by energy dispersive X-ray spectroscopy ("EDS").

[0264] like Figure 3A As shown in , it was confirmed that residual lithium existed on the surface of the composite positive electrode active material of Comparative Example 1.

[0265] like Figure 3B As shown in , it was confirmed that a Co-containing coating layer having a Li—Co—O composition was formed on the surface of the composite positive electrode active material of Comparative Example 3 coated with the Co-containing component.

[0266] like Figure 3C As shown in FIG. 1 , it is confirmed that the composite positive electrode active material of Comparative Example 4 coated with the Ce-containing component has CeO on its surface. 2The Ce-containing coating layer is composed of

[0267] like Figure 3D and 3E As shown in FIG. 1 , it was confirmed that the composite positive electrode active materials of Examples 1 and 2 each had a Co-containing coating layer having a Li—Co—O composition and a CeO-containing coating layer at its surface. 2 The Ce-containing coating layer is composed of

[0268] Figures 4A to 4C A high-angle annular dark field "(HAADF") scanning transmission electron microscope "(STEM") image and an EDS image of a cross-section of a composite positive electrode active material of Example 1 including a plurality of primary particles aggregated into secondary particles corresponding to a core formed by aggregating primary particles and a coating layer on the core are shown.

[0269] like Figure 4C As shown in FIG. 1 , it was confirmed that the first layer containing Co was formed on the core and the primary particles included in the core. Although not shown in the figure, it was confirmed that the second layer containing Ce was additionally provided on the Co-containing coating layer.

[0270] In addition, refer to Figure 4C , confirming that the Co concentration in the first layer is greater than that in the primary particles. Figure 4B and 4C In the embodiment, the higher the concentration of the metal, the brighter the color corresponding to the metal. That is, it was confirmed that the coating layer containing a high concentration of Co was formed on the primary particles included in the core. Figure 4C As shown in , the thickness of the first layer is about 20 nanometers (nm).

[0271] Although not shown in the figure, through additional high-resolution analysis, it was confirmed that there were separate phases containing Zr on the surface of the core and grain boundaries between primary particles in the core. The separate phase was Li+ with a monoclinic crystal structure belonging to the C2 / m space group. 2 ZrO 3 Mutually.

[0272] Although not shown in the drawings, it was confirmed that the composite cathode active material of Example 3 was formed in the form of a single layer of a composite coating layer containing both Co and Ce on the surface of the core.

[0273] Evaluation Example 3: Evaluation of Residual Lithium Content

[0274] The amount of surface residual lithium of each of the composite cathode active materials of Examples 1-2 and Comparative Example 1 was measured, and some of the results are shown in Table 1 below.

[0275] The amount of residual lithium on the surface was evaluated by measuring the amount of Li remaining on the surface of the composite positive electrode active material by a wet method (or titration method). 2 CO3 and the Li content in LiOH.

[0276] For a specific measurement method, refer to the method disclosed in paragraph

[0054] of Japanese Patent Laid-Open Publication No. 2016-081903.

[0277] Table 1

[0278] Residual lithium content (ppm) Comparative Example 1 4514 Example 1 1123 Example 2 1432

[0279] As shown in Table 1, it was confirmed that the residual lithium content of each of the composite positive electrode active materials of Examples 1 and 2 was smaller than the residual lithium content of the composite positive electrode active material of Comparative Example 1.

[0280] It is considered that the residual lithium on the surface of the lithium nickel transition metal oxide sequentially reacts with the precursor of the first component and the precursor of the second component to form a multi-layer coating layer on the core.

[0281] Therefore, compared with the lithium battery including the composite positive electrode active material of Comparative Example 1, the lithium battery including the composite positive electrode active material of Examples 1 and 2 suppressed gas generation during charge and discharge and suppressed side reactions with the electrolyte solution, resulting in improved life characteristics.

[0282] Evaluation Example 4: Differential Scanning Calorimetry (DSC) Measurement of Composite Cathode Active Material

[0283] Regarding the composite positive active materials of Example 1 and Comparative Examples 3 and 4, DSC thermograms were measured at temperatures of 30° C. to 350° C., and the results are shown in Table 2 below.

[0284] Table 2

[0285]

[0286]

[0287] As shown in Table 2, the composite positive electrode active material of Example 1 including the first and second components has a lower calorific value than each of the composite positive electrode active materials of Comparative Examples 3 and 4 including the first component or the second component.

[0288] Therefore, it was confirmed that the composite cathode active material of Example 1 had improved thermal stability compared with the composite cathode active materials of Comparative Examples 3 and 4.

[0289] Evaluation Example 5: Evaluation of High Temperature Stability of Composite Cathode Active Materials

[0290] The lithium batteries (open circuit voltage ("OCV"), 4.35 V) of Example 10 and Comparative Examples 11 and 13 were charged to a voltage of 100% of the state of charge ("SOC") at a current of 0.1 C at a temperature of 45° C. After cutoff, the charged lithium batteries were stored in an oven at 60° C. for 7 days, and then high temperature stability was evaluated by measuring the concentration of metal ions eluted in the electrolyte solution.

[0291] Table 3

[0292]

[0293] As shown in Table 3, compared with the lithium batteries of Comparative Examples 11 and 13, the metal ion leakage in the lithium battery of Example 10 was suppressed.

[0294] It can be seen that the suppression of metal ion leakage is due to the stabilized coating layer caused by including the second layer in the composite positive electrode active material in Example 10, while the composite positive electrode active materials of Comparative Examples 11 and 13 do not include the second layer.

[0295] For example, it can be seen that because the second layer acts as a protective layer, it is considered that the leakage of metal ions is more effectively suppressed at high temperatures.

[0296] Evaluation Example 6: Evaluation of charging and discharging characteristics at room temperature

[0297] The lithium batteries of Examples 5-8 and Comparative Examples 5-8 were subjected to constant current charging at a current rate of 0.1C at a temperature of 25°C until the voltage reached 4.35 volts (V) (relative to Li / Li + ), then maintained at 4.35V in constant voltage mode and cut off at a current rate of 0.05C. Then, it was discharged at a constant current rate of 0.1C until the voltage reached 2.8V (relative to Li / Li + )(1st cycle, transformed into cycle).

[0298] The lithium battery that has undergone the first cycle was charged at a constant current of 0.5C at a temperature of 25°C until the voltage reached 4.35V (relative to Li / Li + ), and then cut off the current at a rate of 0.05C while maintaining a constant voltage of 4.35V. Then, it was discharged at a constant current rate of 0.2C until the voltage reached 2.8V (relative to Li / Li + )(2nd cycle).

[0299] The lithium battery that has undergone the second cycle is charged at a constant current of 1C at a temperature of 25°C until the voltage reaches 4.35V (relative to Li / Li +), followed by a current cutoff at a rate of 0.05C while maintaining a constant voltage of 4.35V. Then, during discharge, the lithium battery was discharged at a constant current rate of 1C until the voltage reached 2.8V (relative to Li / Li + ) (3rd cycle), and the cycle was repeated under the same conditions (repeated 50 times) until the 52nd cycle.

[0300] In all charge / discharge cycles, there was a rest time of 10 minutes after one charge / discharge cycle.

[0301] Some of the charge-discharge test results are shown in the following Table 4. The capacity retention ratio in the 52nd cycle is defined by the following Equation 1.

[0302] The discharge capacity in the second cycle was taken as the standard capacity.

[0303] Equation 1

[0304] Capacity retention rate (%) = (discharge capacity at the 52nd cycle / discharge capacity at the 3rd cycle) × 100%

[0305] Table 4

[0306]

[0307]

[0308] As shown in Table 4, the lithium batteries of Examples 5 to 8 have improved lifespan characteristics without reducing actual capacity compared to the lithium battery of Comparative Example 6.

[0309] Such improved life characteristics are attributed to the fact that the surface of the composite positive electrode active material included in each of the lithium batteries of Examples 5, 6, 7 and 8 is further stabilized by a multi-layer coating layer or a single-layer composite coating layer, which leads to the suppression of side reactions with the electrolyte solution.

[0310] In addition, the composite positive electrode active material included in each of the lithium batteries of Examples 5 and 6 has a second layer (the second layer is not included in the composite positive electrode active material included in each of the lithium batteries of Comparative Examples 7 and Comparative Example 8), and therefore the second layer effectively suppresses the side reactions of the reaction mixture. For example, Ce and the like in the second layer disposed on the first layer of the composite positive electrode material contained in each of the lithium batteries of Examples 5-6 and 8 are suppressed from mixing with the transition metal contained in the primary particles. Therefore, the nickel ions contained in the composite positive electrode active material are effectively suppressed from leaking into the electrolyte solution. In addition, the interface resistance between the composite positive electrode active material and the electrolyte solution is reduced because the Ce oxide contained in the second layer has both ionic conductivity and electronic conductivity. In addition, since the Ce oxide contained in the second layer has excellent structural thermal stability, the surface of the composite positive electrode active material is stabilized by suppressing side reactions with the electrolyte solution.

[0311] In addition, the lithium battery of Example 5 has improved life characteristics compared to the lithium battery of Example 8. Such improved life characteristics are believed to be due to the fact that, for example, in the composite positive electrode active material included in the lithium battery of Example 5, Li 2 ZrO 3 Also in the grain boundaries between the primary particles inside the core, and due to the coating, side reactions between the primary particles inside the core and the electrolyte and leakage of transition metals from the primary particles are suppressed, and a three-dimensional lithium ion migration channel is obtained through the second phase on the surface of the core and inside the core.

[0312] Evaluation Example 7: Evaluation of high temperature charge and discharge characteristics

[0313] The lithium batteries of Example 10 and Comparative Examples 11-13 were subjected to constant current charging at a current rate of 0.1C at a temperature of 45°C until the voltage reached 4.30V (relative to Li / Li + ), then kept at 4.30V in constant voltage mode and cut off at a current rate of 0.05C. Then, it was discharged at a constant current rate of 0.1C until the voltage reached 2.8V (relative to Li / Li + )(1st cycle, transformed into cycle).

[0314] The lithium battery that has undergone the first cycle was charged at a constant current of 1C at a temperature of 45°C until the voltage reached 4.30V (relative to Li / Li + ), and then cut off the current at a rate of 0.05C while maintaining a constant voltage of 4.30V. Then, it was discharged at a constant current rate of 0.2C until the voltage reached 2.8V (relative to Li / Li + )(2nd cycle).

[0315] The lithium battery that has undergone the second cycle was charged at a constant current of 1C at a temperature of 45°C until the voltage reached 4.30V (relative to Li / Li + ), followed by a current cutoff at a rate of 0.05C while maintaining a constant voltage of 4.30V. Then, during discharge, the lithium battery was discharged at a constant current rate of 1C until the voltage reached 2.8V (relative to Li / Li + ) (3rd cycle), and the cycle was repeated under the same conditions (repeated 100 times) until the 102nd cycle.

[0316] In all charge / discharge cycles, there was a rest time of 10 minutes after one charge / discharge cycle.

[0317] Some of the charge-discharge test results are shown in the following Table 5. The capacity retention ratio in the 102nd cycle is defined by Equation 2 below.

[0318] Equation 2

[0319] Capacity retention rate (%) = (discharge capacity at the 102nd cycle / discharge capacity at the 3rd cycle) × 100%

[0320] Table 5

[0321]

[0322] As shown in Table 5, the lithium battery of Example 10 has improved high temperature life characteristics compared to the lithium batteries of Comparative Examples 11 and 13. In other words, the lithium battery of Example 10 has better thermal stability than the lithium batteries of Comparative Examples 11 and 13.

[0323] The improved high temperature life characteristics are due to stabilization in the coating layer caused by including the second layer in the composite cathode active material in Example 10, while the composite cathode active materials of Comparative Examples 11 and 13 did not include the second layer.

[0324] For example, the second layer acts as a protective layer, which is believed to be more effective in suppressing metal ion leakage, for example, at high temperatures.

[0325] Evaluation Example 8: Evaluation of charge and discharge characteristics at room temperature (LFP 5% addition evaluation)

[0326] The lithium batteries of Examples 5 and 9 were subjected to constant current charging at a current rate of 0.1C at a temperature of 25°C until the voltage reached 4.35V (relative to Li / Li +), then maintained at 4.35V in constant voltage mode and cut off at a current rate of 0.05C. Then, it was discharged at a constant current rate of 0.1C until the voltage reached 2.8V (relative to Li / Li + )(1st cycle, transformed into cycle).

[0327] The lithium battery that has undergone the first cycle was charged at a constant current of 0.5C at a temperature of 25°C until the voltage reached 4.35V (relative to Li / Li + ), and then cut off the current at a rate of 0.05C while maintaining a constant voltage of 4.35V. Then, it was discharged at a constant current rate of 0.2C until the voltage reached 2.8V (relative to Li / Li + )(2nd cycle).

[0328] The lithium battery that has undergone the second cycle is charged at a constant current of 1C at a temperature of 25°C until the voltage reaches 4.35V (relative to Li / Li + ), followed by a current cutoff at a rate of 0.05C while maintaining a constant voltage of 4.35V. Then, during discharge, the lithium battery was discharged at a constant current rate of 0.2C until the voltage reached 2.8V (relative to Li / Li + ) (3rd cycle), and the cycle was repeated under the same conditions (repeated 50 times) until the 52nd cycle.

[0329] In all charge / discharge cycles, there was a rest time of 10 minutes after one charge / discharge cycle.

[0330] Some of the charge-discharge test results are shown in the following Table 6. The capacity retention ratio in the 52nd cycle and the initial charge-discharge efficiency in the 1st cycle are defined by Equations 3 and 4 below.

[0331] The discharge capacity in the second cycle was taken as the standard capacity.

[0332] Equation 3

[0333] Capacity retention rate (%) = (discharge capacity at the 52nd cycle / discharge capacity at the 3rd cycle) × 100%

[0334] Equation 4

[0335] Initial efficiency (%) = (discharge capacity in the first cycle / charge capacity in the first cycle) × 100%

[0336] Table 6

[0337]

[0338] As shown in Table 6, compared with the lithium battery of Example 5, the lithium battery including LiFePO 4 The lithium battery of Example 9 has improved initial charge-discharge efficiency and capacity retention rate.

[0339] Evaluation Example 9: Evaluation of DC resistance ("DC-IR") at room temperature (25°C)

[0340] The initial DC-IR of the lithium batteries of Example 5 and Example 9 was measured at room temperature (25° C.) by using the following method.

[0341] In the first cycle, the lithium battery was charged at a current of 0.5C to a voltage of 50% of the state of charge (SOC), then cut off at 0.02C, followed by a rest period of 10 minutes, and

[0342] The lithium battery was discharged at a constant current of 0.5C for 30 seconds, followed by a rest period of 30 seconds, and then charged at a constant current of 0.5C for 30 seconds, followed by a rest period of 10 minutes, and

[0343] The lithium battery was discharged at 1C constant current for 30 seconds, followed by a 30-second rest, and then charged at 0.5C constant current for 1 minute, followed by a 10-minute rest, and

[0344] The lithium battery was discharged at 2C constant current for 30 seconds, followed by a 30-second rest, and then charged at 0.5C constant current for 2 minutes, followed by a 10-minute rest, and

[0345] The lithium battery was discharged at a constant current of 3C for 30 seconds, then rested for 30 seconds, and then charged at a constant current of 0.5C for 3 minutes, followed by a rest period of 10 minutes.

[0346] The average voltage drop value for each C-rate for 30 seconds is the DC voltage value. The direct current ("DC") resistance at the measured DC voltage was calculated and is shown in Table 7 below.

[0347] Table 7

[0348] Initial DC resistance (mΩ) Example 5 125 Example 9 121

[0349] As shown in Table 7, compared with the lithium battery of Example 5, the lithium ion battery including LiFePO 4 The lithium battery of Example 9 has a reduced initial DC resistance.

[0350] Evaluation Example 10: Evaluation of high temperature charge and discharge characteristics (LFP 5% addition evaluation)

[0351] The lithium batteries of Examples 10 and 14 were subjected to constant current charging at a current rate of 0.1C at a temperature of 45°C until the voltage reached 4.30V (relative to Li / Li +), then kept at 4.30V in constant voltage mode and cut off at a current rate of 0.05C. Then, it was discharged at a constant current rate of 0.1C until the voltage reached 2.8V (relative to Li / Li + )(1st cycle, transformed into cycle).

[0352] The lithium battery that has undergone the first cycle was charged at a constant current of 0.5C at a temperature of 45°C until the voltage reached 4.30V (relative to Li / Li + ), and then cut off the current at a rate of 0.05C while maintaining a constant voltage of 4.30V. Then, it was discharged at a constant current rate of 0.2C until the voltage reached 2.8V (relative to Li / Li + )(2nd cycle).

[0353] The lithium battery that has undergone the second cycle was charged at a constant current of 1C at a temperature of 45°C until the voltage reached 4.30V (relative to Li / Li + ), followed by a current cutoff at a rate of 0.05C while maintaining a constant voltage of 4.30V. Then, during discharge, the lithium battery was discharged at a constant current rate of 1C until the voltage reached 2.8V (relative to Li / Li + ) (3rd cycle), and the cycle was repeated under the same conditions (repeated 100 times) until the 102nd cycle.

[0354] In all charge / discharge cycles, there was a rest time of 10 minutes after one charge / discharge cycle.

[0355] Some of the charge-discharge test results are shown in the following Table 8. The capacity retention ratio in the 102nd cycle is defined by the following Equation 5.

[0356] Equation 5

[0357] Capacity retention rate (%) = (discharge capacity at the 102nd cycle / discharge capacity at the 3rd cycle) × 100%

[0358] Table 8

[0359] Capacity retention rate (%) Example 10 93.1 Embodiment 14 93.6

[0360] As shown in Table 8, compared with the lithium battery of Example 10, the lithium battery including LiFePO 4 The lithium battery of Example 14 has improved high temperature life characteristics.

[0361] In one aspect, the composite cathode active material includes a multi-layer or single-layer composite coating layer including a first metal and a second metal to improve the cycle characteristics and thermal stability of a lithium battery.

[0362] It should be understood that the embodiments described herein should be considered in a descriptive sense only and not for purposes of limitation. Descriptions of features or aspects within each embodiment should typically be considered as available for other similar features or aspects in other embodiments.

[0363] Although one or more embodiments have been described with reference to the drawings, it will be understood by those of ordinary skill in the art that various changes in form and details may be made therein without departing from the spirit and scope as defined by the following claims.

Claims

1. Composite positive electrode active materials, include: a core comprising a plurality of primary particles; and a shell disposed on the core, in The primary particles of the plurality of primary particles include lithium nickel transition metal oxide, and The shell includes a first component and a second component, wherein the first component contains a first metal and the second component contains a second metal, in The first metal includes at least one metal other than nickel belonging to any one of Group 2, Group 4, Group 5, and Group 7 to Group 15 of the periodic table, The second metal comprises a metal of Group 3 of the Periodic Table of Elements, and The first component comprises a first phase and the second component comprises a second phase distinguishable from the first phase, The amount of nickel included in the lithium nickel transition metal oxide is 70 mol % or more based on the total moles of nickel and transition metal in the lithium nickel transition metal oxide, The first component includes a phase having a layered crystal structure, a phase having a spinel crystal structure, or a combination thereof, The second component includes a phase having a fluorite crystal structure.

2. The composite positive electrode active material according to claim 1, wherein wherein the layered crystal structure belongs to space group R-3m, and The spinel crystal structure belongs to the space group Fd-3m. 3 . The composite positive electrode active material according to claim 1 , wherein the fluorite crystal structure belongs to the space group Fm-3m.

4. The composite positive electrode active material according to claim 1, wherein the shell include: A multilayer structure comprising a first layer and a second layer, wherein the first layer comprises a first component, the second layer comprises a second component, and the second layer is located on the first layer; or A single layer structure comprising a third layer, wherein the third layer comprises the first component and the second component.

5. The composite positive electrode active material according to claim 4, wherein the primary particle comprises the first layer or the third layer on the surface of the primary particle, and The concentration of the first metal in the first layer or the third layer is greater than the concentration of the first metal in the primary particles.

6. The composite positive active material of claim 1, wherein the first metal comprises Co, Mg, Zr, Al, Mn, Si, Pd, Ti, Sn, Ir, Pt, Ru, Ca, Ba, V, Nb, Fe, Cu, Ag, Zn, B, Ga, Ge, Sb, Bi, or a combination thereof.

7. The composite positive electrode active material according to claim 1, wherein the first component is a component including the first metal and oxygen, or a component including lithium, the first metal and oxygen, in The amount of lithium is 0 mol to 3.3 mol based on 1 mol of the first component, The amount of the first metal is 0.7 mol to 3.3 mol based on 1 mol of the first component, and The amount of oxygen is 1.7 mol to 4.3 mol based on 1 mol of the first component.

8. The composite positive electrode active material according to claim 1, wherein the first component is represented by Formula 1: Formula 1 Li a M1 b O c In formula 1, M1 is Co, Mg, Zr, Al, Mn, Si, Pd, Ti, Sn, Ir, Pt, Ru, Ca, Ba, V, Nb, Fe, Cu, Ag, Zn, B, Ga, Ge, Sb, Bi, or a combination thereof, and 0≤a≤3.1, 0.9≤b≤3.1, and 1.9≤c≤4.

1.

9. The composite cathode active material according to claim 1, wherein the first component comprises Co 3 O 4 , MgO, Li x CoO 2 , Li 2 ZrO 3 , ZrO 2 , Al 2 O 3 , Li 2 MnO 3 , LiMn 2 O 4 , LiAlO 2 , TiO 2 , Li 2 TiO 3 , Li 2 SnO 3 , SnO, SnO 2 , BaTiO 3 , V 2 O 5 , Nb 2 O 5 , ZnO, B 2 O 3 , Ga 2 O 3 , or a combination thereof. 10 . The composite cathode active material of claim 1 , wherein an amount of the first component or the first metal included in the shell is 10 parts by weight or less based on 100 parts by weight of the lithium nickel transition metal oxide.

11. The composite positive electrode active material according to claim 1, wherein the second component is a component including the second metal and oxygen, in The amount of the second metal is 0.7 mol to 1.3 mol based on 1 mol of the second component, and The amount of oxygen is 1.7 mol to 2.3 mol based on 1 mol of the second component.

12. The composite positive electrode active material according to claim 1, wherein the second component is represented by Formula 2: Formula 2 M2 b About c In Formula 2, M2 is Ce, La, Sc, Y, Nd, Sm, Er, or a combination thereof, and 0.9≤b≤1.1 and 1.9≤c≤2.

1.

13. The composite positive electrode active material according to claim 1, wherein the second component comprises CeO 2 、Ce 2 O 3 、Ce 3 O 4 ,La 2 O 3 Sc 2 O 3 , Y 2 O 3 、Nd 2 O 3 、Sm 2 O 3 , Er 2 O 3 , or a combination thereof. 14 . The composite positive active material of claim 1 , wherein an amount of the second component or the second metal included in the shell is 10 parts by weight or less based on 100 parts by weight of the lithium nickel transition metal oxide. 15 . The composite positive active material of claim 1 , wherein the core includes a grain boundary between primary particles of the plurality of primary particles, and the grain boundary includes a third component including a third metal. 16 . The composite positive active material of claim 15 , wherein the third component includes a third phase having a monoclinic crystal structure, and the structure of the third component belongs to a C2 / m, C12 / c1, or C2 / c space group.

17. The composite positive active material of claim 15, wherein the third metal is Zr, Al, Co, Mg, Mn, Si, Mo, Pd, Ti, Sn, Ir, Pt, Ru, or a combination thereof.

18. The composite positive active material of claim 15, wherein the third component comprises lithium, the third metal, and oxygen, and The amount of lithium is 1.7 mol to 2.3 mol based on 1 mol of the third component, The amount of the third metal is 0.7 mol to 1.3 mol based on 1 mol of the third component, and The amount of oxygen is 2.7 mol to 3.3 mol based on 1 mol of the third component.

19. The composite positive active material according to claim 15, wherein the third component is represented by Formula 3: Formula 3 Read a M3 b Oh c In Formula 3, M3 is Zr, Al, Co, Mg, Mn, Si, Mo, Pd, Ti, Sn, Ir, Pt, Ru, or a combination thereof, and 1.9≤a≤2.1, 0.9≤b≤1.1, and 2.9≤a≤3.

1. 20 . The composite cathode active material of claim 1 , wherein the shell further comprises a third component comprising a third metal.

21. The composite cathode active material according to claim 1, wherein the lithium nickel transition metal oxide comprises a third metal.

22. The composite cathode active material according to claim 1, wherein the lithium nickel transition metal oxide comprises lithium, nickel, a third metal, a fourth metal, and oxygen, and the amount of lithium is from 0.1 mole to 1.3 moles, based on 1 mole of the lithium nickel transition metal oxide, the amount of nickel is from 0.7 mole to 0.99 mole, based on 1 mole of the lithium nickel transition metal oxide, the amount of the third metal is from 0.0005 mole to 0.01 mole, based on 1 mole of the lithium nickel transition metal oxide, the amount of the fourth metal is from 0.01 mole to 0.3 mole, based on 1 mole of the lithium nickel transition metal oxide, and the amount of oxygen is from 1.7 to 2.3 moles, based on 1 mole of the lithium nickel transition metal oxide, and the fourth metal is a metal different from lithium, nickel, and the third metal.

23. The composite cathode active material according to claim 1, wherein the lithium nickel transition metal oxide is represented by Formula 4: Formula 4 Li a M4O 2-α X α wherein in Formula 4, 0.9 ≤ a ≤ 1.2 and 0 ≤ α < 2, M4 comprises nickel, a third metal, and a fourth metal, wherein the fourth metal is an element of Groups 2 to 13 of the periodic table and is different from nickel and the third metal, X is F, S, or P, and the amount of nickel in M4 is from 70 mole % to less than 100 mole %, based on the total content of the lithium nickel transition metal oxide.

24. The composite cathode active material according to claim 1, wherein the lithium nickel transition metal oxide is represented by Formula 5: Formula 5 Li a Ni b M5 c M6 d M7 e O 2-α X α wherein in Formula 5, 0.9 ≤ a ≤ 1.2, 0.7 < b < 1, 0 < c < 0.3, 0 < d < 0.3, 0 ≤ e < 0.1, b + c + d + e = 1, and 0 ≤ α < 2, M5, M6, and M7 are different from each other and are each Co, Mn, Zr, Al, Re, V, Cr, Fe, B, Ru, Ti, Nb, Mo, Mg, or Pt, and X is F, S, or P.

25. The composite cathode active material according to claim 15, wherein the lithium nickel transition metal oxide is represented by Formula 6 or Formula 7: Formula 6 Li a Ni b Co c Mr d M8 e O 2-α X α Formula 7 Li a Ni b Co c Al d M8 e O 2-α X α wherein in Formulas 6 and 7, 0.9 ≤ a ≤ 1.2, 0.7 < b < 1, 0 < c < 0.1, 0 < d < 0.1, 0 ≤ e < 0.01, b + c + d + e = 1, and 0 ≤ α < 2, M8 is Zr, Al, V, Cr, Fe, Re, B, Ru, Ti, Nb, Mo, Mg, or Pt, and X is F, S, or P.

26. The composite cathode active material according to claim 1, wherein the lithium nickel transition metal oxide is represented by Formula 8: Formula 8 aLi 2 MnO 3 ·(1-a)LiMO 2-α X α wherein in Formula 8, 0 < a < 1 and 0 ≤ α < 2, M comprises Ni and Co, Mn, Zr, Al, Re, V, Cr, Fe, B, Ru, Ti, Nb, Mo, Mg, Pt, or a combination thereof, and X is F, S, or P.

27. A cathode comprising the composite cathode active material according to any one of claims 1 - 26. 28 . The positive electrode of claim 27 , further comprising a positive electrode active material having an olivine structure. 29 . The positive electrode of claim 28 , wherein an amount of the positive electrode active material having an olivine structure is less than or equal to 10 wt % based on the total weight of the positive electrode active material.

30. Lithium battery, include: The positive electrode according to any one of claims 27 to 29; negative electrode; as well as An electrolyte is between the positive electrode and the negative electrode.

31. A method for producing a composite positive electrode active material according to any one of claims 1 to 26, wherein the method include: Providing lithium nickel transition metal oxides; contacting a first metal precursor, a second metal precursor, and the lithium nickel transition metal oxide to prepare a mixture; drying the mixture; as well as The dried mixture is heat-treated at a temperature of 400° C. to 1000° C. under an oxidative atmosphere to produce the composite positive active material.

32. The method of claim 31, wherein said providing a lithium nickel transition metal oxide include: contacting the precursor of the lithium nickel transition metal oxide and a third metal precursor to prepare a mixture; as well as The mixture is heat-treated at a temperature of 400° C. to 1000° C. under an oxidizing atmosphere to provide the lithium nickel transition metal oxide.